Winding-type all-solid-state lithium ion secondary battery and method for manufacturing winding-type all-solid-state lithium ion secondary battery
The use of an amorphous lithium-containing oxide with controlled molar ratios in the solid electrolyte layer enhances conductivity and adhesion in all-solid-state lithium-ion secondary batteries, addressing the limitations of existing technologies by improving safety and performance without high-temperature sintering.
Patent Information
- Application Number
- CN202380039026.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-31
- Publication Date
- 2024-12-20
AI Technical Summary
Existing all-solid-state lithium-ion secondary batteries face challenges in achieving high lithium ion conductivity and adhesion between particles without high-temperature sintering treatment, particularly in wound-type batteries, which are crucial for conforming to standardized shapes and volumes.
A wound all-solid-state lithium-ion secondary battery with a solid electrolyte layer composed of an amorphous lithium-containing oxide (Li2+x B 4+y O 7+z) and a lithium salt, where the molar ratios of lithium, boron, oxygen, and other elements are specifically controlled, allowing for excellent adhesion and conductivity without sintering, and optionally containing bound water.
The battery achieves high lithium ion conductivity and safety with improved adhesion between particles, reducing interface resistance and preventing cracks during winding, while eliminating the need for high-temperature sintering and organic polymer binders.
Smart Images

Figure CN119174027A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a wound all-solid-state lithium-ion secondary battery and a method for manufacturing the wound all-solid-state lithium-ion secondary battery. Background Art
[0002] In the past, liquid electrolytes with high ion conductivity have been used in lithium-ion secondary batteries. However, since liquid electrolytes are flammable, there are safety issues. In addition, since they are in a liquid state, it is difficult to make them compact, and when the battery becomes larger, the capacity limitation also becomes a problem.
[0003] In contrast, all-solid-state lithium-ion secondary batteries are one of the next-generation batteries that can solve these problems. The basic structure of an all-solid-state lithium-ion secondary battery is shown in FIG. Figure 1 In the embodiment of the present invention, the all-solid-state lithium-ion secondary battery 10 has a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4 and a positive electrode current collector 5 in order from the negative electrode side. Each layer is in contact with each other and has an adjacent structure. By adopting this structure, during charging, electrons (e - ) is supplied to the negative electrode side, so that the lithium ions (Li + ) accumulates here. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side through the solid electrolyte layer 3, so that the electrons are supplied to the working part 6. In the example shown in the figure, a light bulb is used as a model at the working part 6, and it is lit by discharge.
[0004] As described above, in order to obtain desired charge and discharge characteristics in an all-solid-state lithium ion secondary battery, the solid electrolyte layer needs to have excellent lithium ion conductivity.
[0005] As the solid electrolyte constituting the solid electrolyte layer, a sulfide-based solid electrolyte or an oxide-based solid electrolyte is mainly used.
[0006] Since sulfide-based solid electrolytes are soft and plastically deformable, the particles can be bonded together simply by press molding. Therefore, the interface resistance between the particles of sulfide-based solid electrolytes is low and the ion conductivity is excellent. However, sulfide-based solid electrolytes have the problem of reacting with water to produce toxic hydrogen sulfide.
[0007] In contrast, oxide-based solid electrolytes have the advantage of high safety. However, oxide-based solid electrolytes are hard and not prone to plastic deformation. In order to improve the adhesion between particles of oxide-based solid electrolytes, high-temperature sintering treatment is required, which is limited from the perspectives of battery production efficiency and energy costs. For example, Patent Document 1 discloses a solid electrolyte formed of a lithium-containing oxide composed of specific elements, and it is recorded that the solid electrolyte shows high ion conductivity, but in order to use the lithium-containing oxide as a solid electrolyte sheet, a high-temperature sintering treatment is required.
[0008] As a technology to deal with this problem, for example, Patent Document 2 describes a composite comprising a lithium compound and lithium tetraborate, wherein the lithium compound has a lithium ion conductivity of 1.0×10 -6 S / cm or more, and the reduced two-body distribution function G(r) of the lithium tetraborate obtained from the total X-ray scattering measurement shows a specific distribution. According to the technology described in Patent Document 2, although the composite is composed of a lithium-containing oxide, lithium tetraborate undergoes plastic deformation between lithium compounds to play a role in connecting lithium compounds. Therefore, even if the composite is not subjected to a high-temperature sintering treatment, it can be formed into a lithium ion conductor showing good lithium ion conductivity by a pressurization treatment.
[0009] Previous technical literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2018-052755
[0012] Patent Document 2: International Publication No. 2021 / 193204 Summary of the invention
[0013] Technical issues to be solved by the invention
[0014] Although the composite described in the above patent document 2 is composed of lithium-containing oxide, it has a soft property and can ensure the bonding between particles even without sintering treatment and without admixing binders such as organic polymers, and has properties that cannot be achieved by oxide-based solid electrolytes to date. However, the results of research conducted by the present inventors have found that the conductivity of lithium ions is not sufficient to be practical as a solid electrolyte layer of an all-solid-state lithium-ion secondary battery at this stage, and there is room for improvement in practical application.
[0015] In practical application, all-solid-state lithium-ion secondary batteries usually need to conform to standardized shapes and volumes. In order to achieve high capacity or high output within this limitation, the following is done: the strip-shaped positive electrode and negative electrode are spirally wound across the solid electrolyte layer to increase the electrode area. In this type of wound all-solid-state lithium-ion secondary battery, the solid electrolyte layer needs to have higher flexibility and adhesion.
[0016] The object of the present invention is to provide a wound-type all-solid-state lithium-ion secondary battery and a method for manufacturing the same, wherein the wound-type all-solid-state lithium-ion secondary battery uses a lithium-containing oxide in a solid electrolyte layer, wherein the solid electrolyte layer has excellent adhesion between particles even without high-temperature sintering treatment and, for example, without the addition of a binder such as an organic polymer, the lithium ion conductivity is higher and the safety is also excellent, and cracks are not easily generated during the winding process or in the wound state.
[0017] Means for solving technical problems
[0018] The problems of the present invention are solved by the following means.
[0019] [1]
[0020] A wound all-solid-state lithium-ion secondary battery is formed by winding a laminated body including a positive electrode layer, a solid electrolyte layer and a negative electrode layer in sequence on a core material, wherein:
[0021] The solid electrolyte layer includes an amorphous solid electrolyte, wherein the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O and a lithium salt. In the amorphous solid electrolyte, the ratio of the content of the lithium salt to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio.
[0022] [2]
[0023] The wound all-solid lithium ion secondary battery according to [1], wherein:
[0024] In the amorphous solid electrolyte, the ratio of the content of water to the content of the lithium-containing oxide is 12 or less in terms of molar ratio.
[0025] 〔3〕
[0026] The wound all-solid lithium ion secondary battery according to [2], wherein:
[0027] In the amorphous solid electrolyte, the ratio of the water content to the lithium-containing oxide content is 1 to 12 in terms of molar ratio.
[0028] [4]
[0029] The wound all-solid lithium ion secondary battery according to any one of [1] to [3], wherein
[0030] The lithium-containing oxide comprises Li 2+x B 4+y O 7+z .
[0031] Among them, -0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3.
[0032] 〔5〕
[0033] The wound all-solid lithium ion secondary battery according to any one of [1] to [4], wherein
[0034] The above lithium salt is represented by the following formula (1).
[0035] Formula (1) LiN(R f1 SO2)(R f2 SO2)
[0036] In the formula, R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.
[0037] [6]
[0038] The wound all-solid lithium ion secondary battery according to any one of [1] to [5], wherein
[0039] In the above-mentioned amorphous solid electrolyte, when the molar amount of B is set to 4.00, the molar amount of Li is 1.58 to 3.49, the molar amount of O is 6.23 to 25.00, and the molar amounts of elements other than B, other than Li, and other than O are 0.001 to 10.00, respectively.
[0040] 〔7〕
[0041] The wound all-solid lithium ion secondary battery according to any one of [1] to [6], wherein
[0042] The lithium-containing oxide is an oxide that has been subjected to mechanical grinding treatment.
[0043] 〔8〕
[0044] A wound all-solid-state lithium-ion secondary battery is formed by winding a laminated body including a positive electrode layer, a solid electrolyte layer and a negative electrode layer in sequence on a core material, wherein:
[0045] The above-mentioned solid electrolyte layer contains an amorphous solid electrolyte including Li, B and O. When the molar amount of B in the amorphous solid electrolyte is set to 4.00, the molar amount of Li is 1.58~3.49, the molar amount of O is 6.23~25.00, and the molar amounts of elements other than Li, B and O are 0.001~10.00 respectively.
[0046] 〔9〕
[0047] The method for manufacturing a wound-type all-solid-state lithium-ion secondary battery according to any one of [1] to [8] comprises the following steps:
[0048] The formation of the stacked body is performed under the condition that the solid electrolyte layer is in contact with water.
[0049] In the present invention or the specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0050] Effects of the Invention
[0051] The wound all-solid lithium ion secondary battery of the present invention is a wound all-solid lithium ion secondary battery using a lithium oxide in a solid electrolyte layer, and the solid electrolyte layer has excellent adhesion between particles even without high-temperature sintering treatment, and, for example, without the addition of a binder such as an organic polymer, the lithium ion conductivity is higher, and the safety is also excellent. In addition, cracks are not easily generated in the wound state. In addition, the method for manufacturing the wound all-solid lithium ion secondary battery of the present invention is a preferred method for manufacturing the wound all-solid lithium ion secondary battery of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a cross-sectional view schematically showing an example of the structure of an all-solid-state lithium-ion secondary battery.
[0053] Figure 2 A cross-sectional view schematically showing a preferred embodiment of a wound all-solid-state lithium-ion secondary battery of the present invention and Figure 2 An enlarged cross-sectional view of section A in FIG.
[0054] Figure 3 This is a diagram showing an example of an X-ray diffraction pattern for explaining the X-ray diffraction characteristics of the solid electrolyte (I) used in the present invention.
[0055] Figure 4 This is a diagram showing an example of the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I) used in the present invention.
[0056] Figure 5 The solid electrolyte (I) used in the present invention is solidified at 20°C or 120°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0057] Figure 6 It means that the solid state of lithium tetraborate crystals is carried out at 20℃ or 120℃ 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0058] Figure 7 The solid electrolyte (I) used in the present invention is solidified at 20°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0059] Figure 8 Yes Figure 7 Figure 2 shows the peak waveform separation.
[0060] Fig. 9 This is a diagram showing an example of the Raman spectrum of the solid electrolyte (I) used in the present invention.
[0061] Fig.10 This is a diagram showing the Raman spectrum of lithium tetraborate crystals.
[0062] Fig.11 Graph showing the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of solid electrolyte (I)-1 prepared in Reference Example 1.
[0063] Fig.12 Graph showing the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of powdered Li2B4O7 crystals.
[0064] Fig.13 This is a diagram showing the X-ray diffraction pattern of powdered Li2B4O7 crystals.
[0065] Fig.14 This is a diagram showing the X-ray diffraction pattern of solid electrolyte (I)-2 prepared in Reference Example 2. DETAILED DESCRIPTION
[0066] [Wound-type all-solid-state lithium-ion secondary battery]
[0067] The wound-type all-solid-state lithium-ion secondary battery of the present invention (hereinafter also referred to as "the secondary battery of the present invention") is a wound-type all-solid-state lithium-ion secondary battery formed by winding a laminated body in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are sequentially arranged on a core material. The solid electrolyte layer contains a solid electrolyte of a specific composition in an amorphous state described later.
[0068] With reference to the accompanying drawings, the preferred mode of the layer structure in the secondary battery of the present invention is described. In addition, the accompanying drawings show an example of an embodiment of the present invention, and the present invention is not limited to the mode shown in the accompanying drawings except for the contents specified in the present invention. In addition, the accompanying drawings showing the structure of the battery are schematic diagrams for facilitating the understanding of the present invention, and the configuration, size or relative size relationship of each component does not directly represent the actual relationship.
[0069] Figure 2 1 is a cross-sectional view showing a preferred embodiment of the secondary battery of the present invention. Figure 2 As shown, in the wound (cylindrical) all-solid-state lithium-ion secondary battery 30, a stack 21 formed by sequentially arranging a negative electrode collector 21b, a negative electrode active material layer 21c, a solid electrolyte layer 21d, a positive electrode active material layer 21e and a positive electrode collector 21f is spirally wound around a core material (axis) 22. Figure 2 In the embodiment shown, the laminate 21 has a separator layer 21a on the side of the negative electrode current collector opposite to the solid electrolyte layer side. Therefore, when the laminate 21 is spirally wound around the core material 22, the separator 21a is also arranged on the outside of the positive electrode current collector 21f. That is, Figure 2 The embodiment shown is a battery element in which a negative electrode collector 21b, a negative electrode active material layer 21c, a solid electrolyte layer 21d, a positive electrode active material layer 21e and a positive electrode collector 21f are stacked in this order, with a separator layer 21a interposed therebetween.
[0070] Furthermore, the wound-type all-solid lithium-ion secondary battery 30 includes a battery exterior body 23 serving as a battery container in which the stacked body 21 is inserted.
[0071] The positive electrode collector 21 f of the stack 21 is connected to the battery positive electrode 26 via an electrically connected positive electrode sheet 25 , and the negative electrode collector 21 b is connected to the battery negative electrode 28 via an electrically connected negative electrode sheet 27 .
[0072] Therefore, if according to Figure 2 The battery form shown, more specifically, the secondary battery of the present invention including the separator layer, is as follows, for example.
[0073] A wound all-solid-state lithium-ion secondary battery is formed by sequentially configuring a positive electrode layer, a solid electrolyte layer and a negative electrode layer, and winding a laminated body formed by configuring a separator layer on the side of the positive electrode layer and / or the negative electrode layer opposite to the solid electrolyte layer side on a core material.
[0074] As mentioned above, in Figure 2In the figure, a structure in which the battery element is multilayered with a separator layer 21a is shown, but the secondary battery of the present invention can also be set to a mode without a separator layer 21a. In this case, the secondary battery of the present invention can function as a bipolar secondary battery, for example. A bipolar secondary battery is a secondary battery in which a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer are sequentially stacked while a positive electrode active material layer is arranged on one surface of a collector and a negative electrode active material layer is arranged on the side opposite to the positive electrode active material layer side of the collector. It is a battery form that can achieve compactness and high current.
[0075] In the present invention, the term "wound-type all-solid-state lithium-ion secondary battery formed by winding a laminated body in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are sequentially arranged on a core material" refers to a battery form (for example, a bipolar type) without a separator layer and a battery form such as a battery with a positive electrode layer, a solid electrolyte layer and a negative electrode layer in a sequential manner. Figure 2 There are two battery forms in which the separator layer is configured in this way.
[0076] The size of the secondary battery of the present invention is not particularly limited and can be appropriately set according to the type of device, vehicle, etc. on which the battery is mounted. Figure 2 The length L of the cylindrical longitudinal direction of the laminated body 21 shown is set to 2 to 50 cm. In addition, the diameter of the core material 22 (circle-equivalent diameter when the cross section of the core material 22 is not circular) is preferably set to 3 to 10 mm.
[0077] Next, each layer of the secondary battery of the present invention will be described.
[0078] <Solid electrolyte layer>
[0079] The solid electrolyte layer constituting the secondary battery of the present invention is a layer in which a solid electrolyte of a specific composition in an amorphous state (which has the same meaning as a non-crystalline state or an amorphous state) or a mixture of the solid electrolyte and other components is formed into a layer. The solid electrolyte of the specific composition in the amorphous state includes a lithium-containing oxide (hereinafter also referred to as "lithium-containing oxide") containing Li, B and O and a lithium salt. In the solid electrolyte, the ratio of the content of the lithium salt to the content of the lithium-containing oxide (lithium salt / lithium-containing oxide) is 0.001 to 1.5 in terms of molar ratio. Hereinafter, the solid electrolyte of the specific composition in the above-mentioned amorphous state is also referred to as "solid electrolyte (I)". The solid electrolyte (I) is generally an inorganic solid electrolyte.
[0080] The solid electrolyte (I) is in an amorphous state and exhibits elastic properties that are prone to plastic deformation. As a result, in a solid electrolyte layer comprising a solid electrolyte (I) formed by a pressurization treatment, the adhesion between the solid electrolytes (I) and / or the adhesion between the solid electrolyte (I) and other ion conductors is improved, and the interface resistance can be reduced, thereby obtaining a more excellent ion conductivity. By using the solid electrolyte (I), although it is a highly safe oxide-based solid electrolyte, even without a high-temperature sintering treatment, a lithium ion conductor exhibiting excellent lithium ion conductivity can be formed by a pressurization treatment.
[0081] The solid electrolyte (I) also preferably contains at least bound water. In this case, in the solid electrolyte (I), the ratio of the water content to the lithium-containing oxide content is preferably 12 or less in terms of molar ratio, more preferably 1 to 12, further preferably 2 to 12, and further preferably 3 to 11. Moreover, the molar ratio is also preferably 2 to 10, also preferably 2 to 8, also preferably 2 to 7, and also preferably 3 to 7. Although the reason why the solid electrolyte (I) exhibits high lithium ion conductivity is not yet clear, in the amorphous solid electrolyte (I), a soft hydration layer is easily formed on the surface of the lithium-containing oxide, and a large amount of lithium derived from the lithium salt is contained in the hydration layer. As a result, it is believed that the ion conductivity is further improved.
[0082] Here, in the present invention or the specification, "bound water" refers to water other than water existing as free water or OH groups bonded to lithium-containing oxides. Even if the solid electrolyte (I) contains water, it is in the state of solid particles (including the state in which the solid particles are bonded to each other), and functions as a solid electrolyte of an all-solid-state lithium-ion secondary battery. That is, the solid electrolyte (I) can contain bound water that is not removed or difficult to remove under normal drying conditions. In this solid electrolyte (I), at least a portion of the water exists in the form of bound water. In addition, in the case where the solid electrolyte (I) contains water, as long as it functions as a solid electrolyte of an all-solid-state lithium-ion secondary battery in the state of solid particles (a state that can be processed in the state of powder), free water can be contained. That is, in the present invention, if the solid electrolyte can be treated as a solid particle (solid powder), "all-solid-state lithium-ion secondary battery" also includes a method in which the solid electrolyte contains water. The solid electrolyte used in the present invention, in which the ratio of the water content to the lithium-containing oxide content is 12 or less in molar ratio, is not in a paste or gel state but in a state of solid particles (solid powder).
[0083] In the present invention, the solid electrolyte (I) is in an "amorphous state" when it satisfies the following X-ray diffraction characteristics or the following requirement A-2 in the total X-ray scattering characteristics. That is, when at least one of the following X-ray diffraction characteristics and the following requirement A-2 in the total X-ray scattering characteristics is satisfied, the solid electrolyte (I) is in an "amorphous state".
[0084] (X-ray diffraction characteristics)
[0085] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from X-ray diffraction measurement using CuKα rays, a first peak having a peak top located in the range of a diffraction angle 2θ of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top located in the range of a diffraction angle 2θ of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top located in the range of a diffraction angle 2θ of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top located in the range of a diffraction angle 2θ of 34.4 to 34.8° and a full width at half maximum of 0.65° or less are not present, or
[0086] In the X-ray diffraction pattern, when at least one of the above-mentioned 1st peak, 2nd peak, 3rd peak and 4th peak (hereinafter referred to as "peak X") is present, the intensity ratio of at least one of the peaks X calculated by the intensity measurement method described below is 5.0 or less.
[0087] - Strength measurement method -
[0088] The arithmetic mean of Av1 and Av2 is calculated by calculating the average intensity (Av1) in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of the peak X, and calculating the average intensity (Av2) in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of the peak X. The ratio of the peak intensity at the peak top of the peak X to the arithmetic mean (peak intensity at the peak top of the peak X / arithmetic mean) is taken as the intensity ratio.
[0089] The X-ray diffraction characteristics will be described in more detail.
[0090] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned first peak, second peak, third peak and fourth peak do not exist, the above-mentioned X-ray diffraction characteristics are satisfied and the solid electrolyte (I) is in an amorphous state.
[0091] Furthermore, in the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned peak X is present, when the intensity ratio of at least one peak among the peaks X obtained by the above-mentioned intensity measurement method also satisfies 5.0 or less, the above-mentioned X-ray diffraction characteristics are also satisfied, and the solid electrolyte (I) is in an amorphous state.
[0092] Here, the full width at half maximum (FWHM) of the peak refers to the peak width (°) at a point where the peak intensity at the top of the peak is 1 / 2.
[0093] refer to Figure 3 , the above-mentioned intensity measurement method is explained in more detail.
[0094] Figure 3 This is a diagram showing an example of a peak X appearing in a diffraction pattern obtained from X-ray diffraction measurement using CuKα rays of a solid electrolyte (I). Figure 3 In the diffraction pattern shown, the intensity of the peak top is shown to show a specific peak with an intensity of 1. In the intensity measurement method, as Figure 3 As shown, the average intensity (Av1) in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the peak X, and the average intensity (Av2) in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the peak X. Next, the arithmetic mean of Av1 and Av2 is calculated, and the ratio of intensity 1 to the arithmetic mean is obtained as the intensity ratio. When the above-mentioned X-ray diffraction characteristics are met, it means that there is no crystal structure or almost no crystal structure in the solid electrolyte (I) and it is in an amorphous state.
[0095] That is, the 1st peak to the 4th peak mentioned above are peaks mainly derived from the crystal structure (for example, the crystal structure of lithium tetraborate) in the solid electrolyte, and the absence of these peaks means that it is in an amorphous state. And, even in the case where there is at least one peak in the 1st peak to the 4th peak, the intensity ratio of at least one peak in the peak X that exists is 5.0 or less, which means that in the solid electrolyte (I), there is almost no crystal structure that hinders the effect of the present invention. In addition, for example, the peak derived from a specific component (for example, a lithium salt) sometimes overlaps with any one of the 1st peak to the 4th peak mentioned above. However, in a solid electrolyte in an amorphous state, the 1st peak to the 4th peak usually decreases, so even if it is assumed that the peak caused by the above-mentioned specific component coincidentally overlaps with any one of the 1st peak to the 4th peak to appear a large peak, there is at least one peak X with an intensity ratio below a specified value, which can be said to indicate that the solid electrolyte (I) is in an amorphous state.
[0096] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.
[0097] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, even if none of the above-mentioned first peak, second peak, third peak and fourth peak exists, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is 3.0 or less.
[0098] Among them, even if the above-mentioned first peak, second peak, third peak and fourth peak do not exist, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is less than 2.0.
[0099] In addition, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 21.6 to 22.0° and a half-width of 0.65° or less, the peak with the largest diffraction X-ray intensity is selected as the first peak to determine the above-mentioned X-ray diffraction characteristics.
[0100] Furthermore, in the above-mentioned X-ray diffraction pattern, when there are two or more peaks with peak tops in the range of 25.4 to 25.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the second peak to perform the above-mentioned X-ray diffraction characteristics.
[0101] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 33.4 to 33.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the third peak to determine the above-mentioned X-ray diffraction characteristics.
[0102] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 34.4 to 34.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the fourth peak to determine the above-mentioned X-ray diffraction characteristics.
[0103] (Total X-ray Scattering Properties)
[0104] The solid electrolyte (I) preferably satisfies the following requirement A-1 as the total X-ray scattering property. Furthermore, when the solid electrolyte (I) satisfies the above-mentioned X-ray diffraction property, the solid electrolyte (I) usually satisfies the following requirement A-2.
[0105] - Requirement A-1-
[0106] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), there is a peak located at r The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0, and the peak G(r) of the second peak shows more than 0.8.
[0107] - Requirement A-2-
[0108] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), when r is greater than and The absolute value of G(r) in the following range is less than 1.0.
[0109] When the solid electrolyte (I) satisfies requirements A-1 and A-2, it has a short-range ordered structure related to the interatomic distance of BO and BB, but has almost no long-range ordered structure, so the oxide solid electrolyte itself shows elastic properties that are softer and more susceptible to plastic deformation than conventional lithium-containing oxides. As a result, it is speculated that in the layer containing the solid electrolyte (I) formed by pressure treatment, the adhesion between the solid electrolytes (I) and / or the adhesion between the solid electrolyte (I) and other ion conductors is improved, and the interface resistance can be reduced, thereby obtaining more excellent ion conductivity.
[0110] The requirements A-1 and A-2 will be described in more detail with reference to the drawings.
[0111] Figure 4 An example of the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of the solid electrolyte (I) is shown. Figure 4 The vertical axis is the reduced two-body distribution function obtained by Fourier transform of X-ray scattering, which represents the probability of the existence of an atom at a distance r. The total X-ray scattering measurement can be performed by SPring-8BL04B2 (acceleration voltage 61.4keV, wavelength The scattering intensity I obtained by the experiment is transformed according to the following steps to obtain the reduced two-body distribution function G(r).
[0112] First, the scattering intensity I obs It is represented by the following formula (1). And, as shown in the following formula (2), the structure factor S(Q) is obtained by dividing the coherent scattering I coh It is obtained by dividing by the product of the number of atoms N and the square of the atomic scattering factor f.
[0113] Iobs =I coh +I incoh +I 荧光 (1)
[0114] [Formula 1]
[0115]
[0116] The structure factor S(Q) is used in PDF (Pair Distribution Function) analysis. In the above equation (2), the required intensity is only the coherent scattering I coh . Incoherent scattering I incoh and Fluorescent X-ray I 荧光 can be used to subtract the theoretical formula using a blank measurement and the detector's discriminator from the scattered intensity I obs Minus.
[0117] Coherent Scattering I coh It is expressed by Debye's scattering formula (the following formula (3)) (N: total number of atoms, f: atomic scattering factor, r ij : the interatomic distance between ij).
[0118] [Formula 2]
[0119]
[0120] If we focus on any atom and let the atomic density at a distance r be ρ(r), then the number of atoms existing in a sphere with a radius of r-r+d(r) is 4πr. 2 ρ(r)dr, the above formula (3) is expressed by the following formula (4).
[0121] [Formula 3]
[0122]
[0123] If the average density of atoms is set to ρ0 and the above formula (4) is modified, the following formula (5) can be obtained.
[0124] [Formula 4]
[0125]
[0126] The following formula (6) can be obtained from the above formula (5) and formula (2).
[0127] [Formula 5]
[0128]
[0129] The two-body distribution function g(r) is expressed by the following equation (7).
[0130] [Formula 6]
[0131]
[0132] The following formula (8) can be obtained from the above formula (6) and formula (7).
[0133] [Formula 7]
[0134]
[0135] As mentioned above, the two-body distribution function can be obtained by Fourier transforming the structure factor S(Q). In order to easily observe the medium-range order / long-range order, the two-body distribution function is transformed into a function G(r)=4πr(g(r)-1) to reduce the two-body distribution function ( Figure 4 ). g(r) oscillating around 0 represents the density difference from the average density at each interatomic distance, and when there is a correlation at a specific interatomic distance, the average density becomes higher than 1. Therefore, the distance and coordination number of the element corresponding to the local to the intermediate distance are reflected. If the order disappears, ρ(r) approaches the average density, so g(r) gradually approaches 1. Therefore, in an amorphous structure, since the larger r becomes, the more the order disappears, g(r) becomes 1, that is, G(r) becomes 0.
[0136] In Element A-1, if Figure 4 As shown, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), there is a peak located at r The first peak P1 and the peak top are located at r within the range of In the second peak P2 within the range of , the peak G(r) of the first peak P1 shows a value greater than 1.0 (preferably greater than 1.2), and the peak G(r) of the second peak P2 shows a value greater than 0.8 (preferably greater than 1.0).
[0137] In addition, Figure 4 The peak of the first peak P1 is located at The peak of the second peak P2 is located at
[0138] exist There is a peak at the position of B (boron)-O (oxygen) interatomic distance. There is a peak of the interatomic distance attributed to B (boron)-B (boron) at the position. That is, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in the solid electrolyte (I).
[0139] Furthermore, in Element A-2, if Figure 4 As shown, when r is more than and In the following range, the absolute value of G(r) is less than 1.0. As mentioned above, when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, it means that there is almost no long-range ordered structure in the solid electrolyte (I).
[0140] In addition, in the above-mentioned reduced two-body distribution function G(r), when r is In the following range, there are peaks other than the first peak and other than the second peak.
[0141] The method for making the solid electrolyte (I) into an amorphous state is not particularly limited. For example, there is the following method: in the preparation of the solid electrolyte (I), a lithium-containing oxide subjected to mechanical grinding is used as a raw material of the lithium-containing oxide. The mechanical grinding treatment can also be performed in the presence of a lithium salt.
[0142] -Mechanical grinding process-
[0143] Mechanical grinding treatment refers to a process of pulverizing a sample while imparting mechanical energy to the sample. As mechanical grinding treatment, for example, a ball mill, a vibration mill, a turbine mill and a disc mill can be mentioned. From the viewpoint of obtaining an amorphous solid electrolyte (I) with good productivity, a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be mentioned, and a planetary ball mill is more preferred.
[0144] The conditions of the ball milling treatment can be appropriately adjusted according to the treatment object. The material of the grinding ball (medium) is not particularly limited, for example, agate, silicon nitride, zirconium oxide, aluminum oxide and iron alloys can be mentioned, preferably yttria stabilized zirconia (YSZ). The average particle size of the grinding ball is not particularly limited. From the perspective of being able to manufacture the solid electrolyte (I) with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is the value obtained by randomly measuring the diameters of 50 grinding balls and arithmetically averaging these. In the case where the grinding ball is not spherical, the major diameter is set as the diameter. The number of grinding balls is not particularly limited.
[0145] The material of the pulverizing pot in the ball milling treatment is not particularly limited, and examples thereof include agate, silicon nitride, zirconium oxide, aluminum oxide, and iron-based alloys, and yttria-stabilized zirconia (YSZ) is preferred.
[0146] The rotation speed of the ball milling process is not particularly limited, and can be set to 200 to 700 rpm, more preferably 350 to 550 rpm. The treatment time of the ball mill is not particularly limited, and can be set to 10 to 200 hours, more preferably 20 to 140 hours. The atmosphere of the ball milling process can be the atmosphere or an inert gas (e.g., argon, helium, nitrogen, etc.) atmosphere.
[0147] In the production of the solid electrolyte (I), it is preferred to perform the following step 1, step 2, and step 3 from the viewpoint of mixing efficiency.
[0148] Step 1: a step of subjecting the lithium-containing oxide to mechanical milling.
[0149] Step 2: A step of mixing the micronized lithium-containing oxide obtained in step 1 with a lithium salt.
[0150] Step 3: A step of further subjecting the mixture obtained in step 2 to mechanical milling.
[0151] In the above step 2, the lithium salt may be added all at once, or may be added in multiple portions while performing the mechanical milling treatment.
[0152] In step 2, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.
[0153] When the solid electrolyte (I) contains at least water as bound water, it is preferred to carry out the following steps 1A to 3A in the production of the solid electrolyte (I).
[0154] Step 1A: A step of mechanically grinding a lithium-containing oxide in the presence of a lithium salt
[0155] Step 2A: Step of mixing the product obtained in step 1A with water
[0156] Step 3A: A step of removing water from the dispersion obtained in step 2A to obtain a solid electrolyte (I)
[0157] In step 1A, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.
[0158] In the above step 2A, the amount of water used is not particularly limited. For example, the amount of water used can be 10 to 200 parts by mass, more preferably 50 to 150 parts by mass, based on 100 parts by mass of the product obtained in step 1A.
[0159] The method of mixing the product obtained in step 1A and water is not particularly limited, and they can be mixed together or water can be added to the product obtained in step 1A in stages for mixing. During mixing, ultrasonic treatment can be performed as needed. The time of ultrasonic treatment is not particularly limited, and can be set to 10 minutes to 5 hours, for example.
[0160] Step 3A is a step of removing water from the dispersion obtained in step 2A to obtain solid electrolyte (I). The method for removing water from the dispersion obtained in step 2A is not particularly limited, and water can be removed by heating treatment or vacuum drying treatment.
[0161] Prior to the step 1A, a step 0 of subjecting the lithium-containing oxide to mechanical milling in an environment without the presence of a lithium salt may be performed.
[0162] When the solid electrolyte (I) contains at least water as bound water, in the production of the solid electrolyte (I), it is also preferable to perform the following steps 1B to 3B instead of the above steps 1A to 3A.
[0163] Step 1B: Mechanical grinding of lithium-containing oxide
[0164] Step 2B: Step of mixing the product obtained in step 1B, water and lithium salt
[0165] Step 3B: A step of removing water from the dispersion obtained in step 2B to obtain a solid electrolyte (I)
[0166] The difference between step 1B and step 1A is that in step 1A, the mechanical milling treatment is carried out in the presence of a lithium salt, whereas in step 1B, the mechanical milling treatment is carried out without using a lithium salt. Therefore, in step 2B, the product obtained in step 1B, water, and a lithium salt are mixed.
[0167] The steps of step 2B are not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a lithium salt all together (method 1), a method of mixing the product obtained in step 1B and water to prepare a dispersion, and then mixing the obtained dispersion with a lithium salt (method 2), or a method of mixing the product obtained in step 1B and water to prepare a dispersion 1, mixing a lithium salt and water to prepare a solution 2, and then mixing the dispersion 1 and the solution 2 (method 3). When mixing the product obtained in step 1B and water, a dispersion treatment such as an ultrasonic treatment may be appropriately performed.
[0168] In method 2, when the dispersion obtained by mixing the product obtained in step 1B and water and the lithium salt are mixed, if there is too much lithium salt, the obtained liquid is easily gelled, and the mixing amount of the lithium salt is limited. In contrast, in method 3, even if the product obtained in step 1B and the lithium salt are mixed in approximately equimolar amounts, the liquid is not easily gelled, and the mixing amount of the lithium salt can be further increased. From this point of view, method 3 is preferred.
[0169] Step 3B is the same as step 3A.
[0170] When the solid electrolyte (I) contains at least water as bound water, in the production of the solid electrolyte (I), it is also preferable to perform the following steps 1C to 3C instead of the above steps 1A to 3A.
[0171] Step 1C: Step of mechanically grinding the lithium-containing oxide
[0172] Step 2C: Step of mixing the product obtained in step 1C with water
[0173] Step 3C: A step of mixing a product obtained by removing water from the dispersion obtained in step 2C with a lithium salt to obtain a solid electrolyte (I)
[0174] Step 1C is the same as step 1B.
[0175] Step 2C is the same as step 2A.
[0176] Step 3C is different from Steps 3A and 3B in that a product obtained by removing water from the dispersion obtained in Step 2C and a lithium salt are mixed.
[0177] In step 3C, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.
[0178] The method of mixing the product obtained by removing water from the dispersion obtained in step 2C and the lithium salt is not particularly limited, and may be a method of immersing a solution obtained by dissolving the lithium salt in water in the product and mixing the two.
[0179] (Component composition of solid electrolyte (I))
[0180] As described above, the solid electrolyte (I) used in the present invention is an amorphous solid electrolyte, and in the solid electrolyte (I), the content of the lithium salt relative to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio.
[0181] When the solid electrolyte (I) does not substantially contain water (for example, when no water is added in addition to the lithium oxide and the lithium salt in the preparation process of the solid electrolyte (I)), the ratio of the content of the lithium salt in the solid electrolyte (I) to the content of the lithium oxide is preferably 0.002 to 1.4, more preferably 0.005 to 1.3 in terms of molar ratio.
[0182] Furthermore, when the solid electrolyte (I) contains at least water as bound water (for example, when water is admixed in addition to lithium oxide and lithium salt in the preparation process of the solid electrolyte (I)), the ratio of the content of lithium salt in the solid electrolyte (I) to the content of lithium oxide is preferably 0.001 to 1.2 in terms of molar ratio, more preferably 0.01 to 1.2, further preferably 0.1 to 1.2, and particularly preferably 0.5 to 1.2.
[0183] Furthermore, when the solid electrolyte (I) contains at least bound water (for example, when water is mixed in addition to the lithium-containing oxide and the lithium salt in the preparation process of the solid electrolyte (I)), the ratio of the content of water in the solid electrolyte (I) to the content of the lithium-containing oxide is preferably 12 or less, more preferably 1 to 12, further preferably 2 to 12, and further preferably 3 to 11 in terms of molar ratio. Furthermore, the molar ratio is also preferably 2 to 10, also preferably 2 to 8, also preferably 2 to 7, and also preferably 3 to 7.
[0184] The molar amounts of the lithium-containing oxide, lithium salt and water in the solid electrolyte (I) can be determined by elemental analysis.
[0185] When the solid electrolyte (I) contains at least bound water (for example, when water is mixed in addition to lithium oxide and lithium salt in the preparation process of the solid electrolyte (I)), the water content in the solid electrolyte (I) is preferably 50% by mass or less, more preferably 45% by mass or less, further preferably 40% by mass or less, and further preferably 35% by mass or less. In addition, the water content in the solid electrolyte (I) is also preferably 30% by mass or less, and also preferably 25% by mass or less.
[0186] Furthermore, when the solid electrolyte (I) contains at least bound water (for example, when water is mixed in addition to lithium oxide and lithium salt in the preparation process of the solid electrolyte (I)), the content of water in the solid electrolyte (I) is usually 5% by mass or more, preferably 10% by mass or more, and preferably 15% by mass or more. Therefore, when the solid electrolyte (I) contains at least bound water (for example, when water is mixed in addition to lithium oxide and lithium salt in the preparation process of the solid electrolyte (I)), the content of water in the solid electrolyte (I) is preferably 5 to 50% by mass, more preferably 5 to 45% by mass, further preferably 10 to 40% by mass, further preferably 10 to 35% by mass, also preferably 10 to 30% by mass, also preferably 15 to 30% by mass, and also preferably 15 to 25% by mass.
[0187] When the solid electrolyte (I) contains at least bound water (for example, when water is mixed in addition to the lithium oxide and the lithium salt in the preparation process of the solid electrolyte (I)), the content of the lithium oxide in the solid electrolyte (I) is preferably 20 to 80% by mass, more preferably 20 to 75% by mass, and further preferably 25 to 70% by mass.
[0188] Furthermore, when the solid electrolyte (I) contains at least bound water (for example, when water is mixed in addition to lithium oxide and lithium salt in the preparation process of the solid electrolyte (I)), the content of lithium salt in the solid electrolyte (I) is preferably 0.5 to 60 mass %, more preferably 1.0 to 55 mass %, further preferably 2.0 to 50 mass %, and also preferably 5.0 to 50 mass %.
[0189] -Contains lithium oxide-
[0190] As described above, the lithium-containing oxide constituting the solid electrolyte (I) contains Li, B, and O.
[0191] The lithium-containing oxide is preferably composed of Li 2+x B 4+y O 7+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). That is, when the molar amount of B is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 2.49 (i.e., 1.7×4 / 4.3 to 2.3×4 / 3.7), and the molar amount of O is 6.23 to 7.89 (i.e., 6.7×4 / 4.3 to 7.3×4 / 3.7). In other words, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 2.49, and the molar amount of O is 6.23 to 7.89. As such a lithium-containing oxide, typically lithium tetraborate (Li2B4O7) can be cited.
[0192] Furthermore, the lithium-containing oxide is preferably composed of Li 1+x B 3+y O 5+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). Such lithium-containing oxides typically include lithium triborate (LiB3O5).
[0193] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 11+y O 18+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3) is a compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B 11 O 18 .
[0194] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 7+y O 12+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B7O is typically mentioned. 12 .
[0195] Therefore, the lithium-containing oxide is preferably the Li 2+x B 4+y O 7+z , the above Li 1+x B 3+y O 5+z , Li 3+x B 11+y O 18+z Li 3+x B 7+y O 12+z At least one of the following.
[0196] Furthermore, LiBO5, Li2B7O 12 , LiB2O3(OH)H2O and Li4B8O 13 At least one of (OH)2(H2O)3 and the like is used as the lithium-containing oxide.
[0197] In the solid electrolyte (I), the lithium-containing oxide is in an amorphous state. That is, the lithium-containing oxide in the solid electrolyte (I) is also in a desired amorphous state so that the solid electrolyte (I) is in the above-mentioned amorphous state.
[0198] Among them, the lithium-containing oxide is preferably lithium tetraborate in an amorphous state.
[0199] -Lithium salts-
[0200] The lithium salt constituting the solid electrolyte (I) used in the present invention is not particularly limited, and examples thereof include Li + and anions, preferably Li + and an organic anion, more preferably a salt composed of Li + And salts composed of organic anions having halogen atoms.
[0201] The lithium salt constituting the solid electrolyte (I) used in the present invention preferably contains two or more specific elements selected from the group consisting of elements of Group 3 of the periodic table, elements of Group 4 of the periodic table, elements of Group 13 of the periodic table, elements of Group 14 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table and H.
[0202] As the lithium salt constituting the solid electrolyte (I) used in the present invention, for example, a compound represented by the formula (1) is preferred.
[0203] Formula (1) LiN(R f1 SO2)(R f2 SO2)
[0204] R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.
[0205] R f1 and R f2 In the case of a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited.
[0206] R f1 and R f2 It is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and still more preferably a halogen atom. If the volume of the terminal group increases, the steric hindrance increases, which becomes a factor that hinders ion conduction. Therefore, R f1 and R f2 In the case of a perfluoroalkyl group, the one having a smaller number of carbon atoms is preferred.
[0207] The lithium salt that can be contained in the solid electrolyte (I) used in the present invention is not limited to the compound represented by the above formula (1). The lithium salt that can be contained in the solid electrolyte (I) used in the present invention is exemplified below.
[0208] (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6 and LiSbF6; perhalide salts such as LiClO4, LiBrO4 and LiIO4; inorganic chloride salts such as LiAlCl4.
[0209] (L-2) Fluorine-containing organic lithium salts: perfluoroalkyl sulfonates such as LiCF3SO3; fluorosulfonyl imide salts or perfluoroalkyl sulfonyl imide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2 (also recorded as Li(FSO2)2N in this specification) and LiN(CF3SO2)(C4F9SO2); perfluoroalkyl sulfonyl methyl salts such as LiC(CF3SO2)3; fluoroalkyl fluorophosphates (preferably perfluoroalkyl fluorophosphates) such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2] and Li[PF3(CF2CF2CF2CF3)3].
[0210] (L-3) Oxalate borate: lithium bis(oxalato)borate and lithium difluorooxalatoborate.
[0211] In addition to the above, LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li2CO3, CH3COOLi, LiAsF6, LiSbF6, LiAlCl4 and LiB(C6H5)4 can also be mentioned.
[0212] Among them, LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(R f11 SO2)、LiN(R f11 SO2)2, LiN(FSO2)2 or LiN(R f11 SO2)(R f12 SO2), more preferably LiPF6, LiBF4, LiN(R f11 SO2)2, LiN(FSO2)2 or LiN(R f11 SO2)(R f12 SO2). In these examples, R f11 and R f12 Each independently represents a perfluoroalkyl group and has preferably 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms, and further preferably 1 or 2. Furthermore, LiNO 3 and 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonylimide lithium are also preferred as the lithium salt.
[0213] From the viewpoint of further improving lithium ion conductivity, in the solid electrolyte (I) of the present invention, the ratio of the content of lithium salt to the content of lithium-containing oxide is preferably 0.001 to 1.2 in terms of molar ratio, more preferably 0.01 to 1.2, further preferably 0.1 to 1.2, and particularly preferably 0.5 to 1.2.
[0214] (Elemental composition of solid electrolyte (I))
[0215] The solid electrolyte (I) has been described based on the components of the compounds constituting the solid electrolyte (I). Next, the solid electrolyte (I) will be described from the viewpoint of a preferred elemental composition.
[0216] The solid electrolyte (I) used in the present invention preferably has a molar amount of Li of 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.80 to 3.00) when the molar amount of B in the solid electrolyte (I) is 4.00. Furthermore, when the molar amount of B in the solid electrolyte (I) is 4.00, the molar amount of O is preferably 6.23 to 25.00 (preferably 6.50 to 23.00, more preferably 8.00 to 23.00, further preferably 10.00 to 23.00, further preferably 10.00 to 18.00). Furthermore, when the molar amount of B in the solid electrolyte (I) is 4.00, the molar amounts of elements other than B, other than Li, and other than O are preferably 0.001 to 10.00 (preferably 0.005 to 6.00, more preferably 0.01 to 5.00), respectively.
[0217] The content of each element is determined by conventional elemental analysis. As a method of elemental analysis, for example, Li and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), N and the like are analyzed by an inert gas fusion method, and for example, F and S are analyzed by combustion ion chromatography. For O, the analysis masses of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Taking into account the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.
[0218] Based on the content of each element calculated by elemental analysis, the molar amounts of Li, O, and other elements when the molar amount of B is set to 4.00 were calculated.
[0219] In a preferred embodiment of the solid electrolyte (I), the solid electrolyte (I) includes, in addition to Li, B and O, one or more elements (E) selected from the group consisting of elements of Group 4, Group 15, Group 16, Group 17, Si, C, Sc and Y, and more preferably includes two or more elements. Among them, it is preferred to include one or more elements (E) selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and more preferably includes two or more elements (E) selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N.
[0220] Examples of the Group 4 elements of the periodic table include Ti, Zr, Hf and Rf. Examples of the Group 15 elements of the periodic table include N, P, As, Sb, Bi and Mc. Examples of the Group 16 elements of the periodic table include S, Se, Te, Po and Lv. Examples of the Group 17 elements of the periodic table include F, Cl, Br, I, At and Ts.
[0221] The number of the element (E) contained in the solid electrolyte (I) may be 3 or more, preferably 2 to 5, and more preferably 2 to 4.
[0222] The second embodiment of the solid electrolyte (I) preferably contains two or more elements (E) selected from F, S, N, P and C, more preferably contains two or more elements (E) selected from F, S, C and N, and further preferably contains three elements (E) of F, S and N.
[0223] In the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.49. That is, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 3.49. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.00, and more preferably 1.80 to 3.00.
[0224] In the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.23 to 25.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of O is preferably 6.23 to 25.00. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.50 to 23.00, more preferably 8.00 to 23.00, further preferably 10.00 to 23.00, and further preferably 10.00 to 18.00.
[0225] In a solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 10.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of each element (E) is preferably 0.001 to 10.00. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.005 to 6.00, and more preferably 0.01 to 5.00.
[0226] As one of the preferred aspects of the elemental composition of the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), it is possible to cite a solid electrolyte (I) containing Li, B, O, F, S and N, and when the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.80 to 3.00), and the molar amount of O is 6.23 to 25.00 (preferably 6.50 to 23.00). 00, more preferably 8.00-23.00, further preferably 10.00-23.00, further preferably 10.00-18.00), the molar amount of F is 0.001-10.00 (preferably 0.01-10.00), the molar amount of S is 0.001-2.00 (preferably 0.01-2.00), and the molar amount of N is 0.001-2.00 (preferably 0.005-1.00) of the solid electrolyte.
[0227] Here, in the solid electrolyte (I), the atoms constituting the above-mentioned lithium salt may exist in the form of doping in the lithium-containing oxide. For example, the solid electrolyte (I) is obtained via the above-mentioned steps 1, 2 and 3. In this case, the lithium salt blended in the preparation of the solid electrolyte (I) sometimes contains a substance that no longer exists in the form of a lithium salt in the solid electrolyte (I), but this solid electrolyte is also included in the solid electrolyte (I). In other words, in one embodiment of the secondary battery of the present invention, having "lithium-containing oxide" and "lithium salt" is not a specific matter of the invention, but can be determined by elemental composition, for example, as follows.
[0228] A wound all-solid-state lithium-ion secondary battery is formed by winding a laminated body including a positive electrode layer, a solid electrolyte layer and a negative electrode layer in sequence on a core material, wherein:
[0229] The above-mentioned solid electrolyte layer contains an amorphous solid electrolyte containing Li, B and O. When the molar amount of B in the amorphous solid electrolyte is set to 4.00, the molar amount of Li is 1.58-3.49 (preferably 1.58-3.00, more preferably 1.80-3.00), the molar amount of O is 6.23-25.00 (preferably 6.50-23.00, more preferably 8.00-23.00, further preferably 10.00-23.00, further preferably 10.00-18.00), and the molar amounts of elements other than Li, B and O are 0.001-10.00 (preferably 0.005-6.00, more preferably 0.01-5.00).
[0230] In the wound all-solid lithium ion secondary battery determined according to the above-mentioned element composition, the "elements other than Li and B and other than O" are as described above, preferably including one or more elements (E) selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc, Y and H, and more preferably including two or more elements. Among them, preferably including one or more elements (E) selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and more preferably including two or more elements (E) selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N.
[0231] Therefore, a more preferable embodiment of the wound-type all-solid lithium-ion secondary battery determined based on the above-mentioned element composition can be determined as follows.
[0232] A wound all-solid-state lithium-ion secondary battery, wherein the solid electrolyte layer comprises an amorphous solid electrolyte, the amorphous solid electrolyte comprises Li, B and O, and comprises one or more (preferably two or more) elements (E) selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc and Y as elements other than Li, B and O, and when the molar amount of B in the amorphous solid electrolyte is set to 4.00 In this case, the molar amount of Li is 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.80 to 3.00), the molar amount of O is 6.23 to 25.00 (preferably 6.50 to 23.00, more preferably 8.00 to 23.00, further preferably 10.00 to 23.00, further preferably 10.00 to 18.00), and the molar amount of element (E) is 0.001 to 10.00 (preferably 0.005 to 6.00, more preferably 0.01 to 5.00).
[0233] Furthermore, a further preferred embodiment can be determined as follows.
[0234] A wound all-solid-state lithium-ion secondary battery, wherein the solid electrolyte layer comprises an amorphous solid electrolyte, the amorphous solid electrolyte comprises Li, B and O, and comprises one or more (preferably two or more) elements (E) selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and when the molar amount of B in the amorphous solid electrolyte is set to 4.00, the molar amount of Li is The molar amount of O is 6.23-25.00 (preferably 6.50-23.00, more preferably 8.00-23.00, further preferably 10.00-23.00, further preferably 10.00-18.00), and the molar amount of element (E) is 0.001-10.00 (preferably 0.005-6.00, more preferably 0.01-5.00).
[0235] The solid electrolyte (I) used in the present invention is the above-mentioned amorphous solid electrolyte. As a result, it is preferred that the solid electrolyte (I) exhibits the following characteristics in addition to the above-mentioned X-ray diffraction characteristics.
[0236] (Solid State 7 Li-NMR spectral characteristics)
[0237] Regarding the solid electrolyte (I), the solid electrolyte (I) was solidified at 20°C and 120°C.7 The full width at half maximum ratio calculated from the spectrum obtained by Li-NMR measurement by the following method is preferably 70% or less, more preferably 60% or less, further preferably 50% or less, further preferably 40% or less, further preferably 35% or less. The lower limit is not particularly limited, but is 10% or more in most cases.
[0238] The above-mentioned half-peak full width ratio is obtained by the following calculation: The solid electrolyte (I) is solidified at 20°C and 120°C respectively. 7 Li-NMR measurement, and after obtaining the half-maximum width (full width at half maximum 1) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 20°C and the half-maximum width (full width at half maximum 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 120°C, the percentage of the ratio of the half-maximum width 2 to the half-maximum width 1 is calculated {(full width at half maximum 2 / full width at half maximum 1) × 100}. The full width at half maximum (FWHM) of the peak refers to the width (ppm) at the 1 / 2 point (H / 2) of the height (H) of the peak.
[0239] Below, use Figure 5 The above characteristics are explained below. Figure 5 In the figure, the solid electrolyte (I) is prepared at 20°C or 120°C. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 5 The solid line spectrum shown on the lower side is the solid state spectrum at 20°C. 7 The spectrum obtained during Li-NMR measurement is Figure 5 The dotted spectrum shown on the upper side is a spectrum obtained by solid-state heating at 120°C. 7 Spectra obtained during Li-NMR measurement.
[0240] Generally speaking, in solid 7 In Li-NMR measurement, Li + In case of high mobility, the peak obtained is sharper. Figure 5 In the manner shown, when comparing the spectrum at 20°C with the spectrum at 120°C, the spectrum at 120°C becomes sharper. Figure 5 In the embodiment shown, it is shown that Li + It is believed that the solid electrolyte (I) is prone to plastic deformation due to the defective structure as described above, and Li + Excellent jumping performance.
[0241] For reference, regarding ordinary lithium tetraborate crystals, solid-state 7 During Li-NMR measurement, Figure 6 The spectrum measured at 20°C is shown by the solid line at the bottom of Figure 6 The spectra measured at 120° C. indicated by the dotted line shown above tend to have substantially the same shape. That is, in the lithium tetraborate crystal, there are no Li defects or the like, and as a result, the elastic modulus is high and plastic deformation is not easily caused.
[0242] The above solid 7 Li-NMR measurement conditions are as follows.
[0243] The measurement was performed using a 4 mm HX CP-MAS probe by a single pulse method with a 90° pulse width of 3.2 μs, an observation frequency of 155.546 MHz, an observation width of 1397.6 ppm, a repetition time of 15 seconds, a cumulative integration of 1 time, and a MAS rotation speed of 0 Hz.
[0244] Furthermore, the solid electrolyte (I) used in the present invention is preferably as follows: 7 When the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is subjected to waveform separation, there is a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of less than 5 ppm, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the above-mentioned area intensity is more preferably 2% or more, more preferably 5% or more, further preferably 10% or more, and further preferably 15% or more. In the case where the solid electrolyte (I) contains at least water as bound water, the solid electrolyte (I) is preferably 7 The Li-NMR spectrum characteristics are as described above. The upper limit of the ratio of the area intensity is not particularly limited, but is often 50% or less.
[0245] Below, use Figure 7 and Figure 8 The above characteristics are described.
[0246] exist Figure 7 The solid electrolyte (I) is shown in FIG. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 7 As shown, a peak (corresponding to the first peak) is observed in the solid electrolyte (I) in the range of -100 to +100 ppm, and in the first peak, a small peak surrounded by a dotted line is observed near the chemical shift of 0 ppm. +When the mobility is high, a sharp peak can be observed, thus producing its influence.
[0247] Then, in Figure 8 , a diagram showing the separation of the first peak waveform is shown. Figure 8 As shown, the first peak is separated into a small peak (corresponding to the second peak) represented by a solid line and a large peak represented by a dotted line. The second peak is a peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of less than 5 ppm.
[0248] The solid electrolyte (I) is preferably composed of Figure 8 The solid line represents the area intensity of the second peak relative to that of Figure 7 The ratio of the area intensity of the first peak (the peak before the waveform separation) {(area intensity of the second peak / area intensity of the first peak)×100} represented is within the above range.
[0249] As a method of waveform separation, a method using known software can be mentioned. As software, for example, Igor Pro, a graphics processing software of WaveMetrics, Inc. can be mentioned.
[0250] (Raman spectroscopy characteristics)
[0251] Regarding the solid electrolyte (I), in the Raman spectrum of the solid electrolyte (I), 600 to 850 cm -1 In the wave number region, the coefficient of determination obtained by linear regression analysis by the least square method is preferably 0.9400 or more, more preferably 0.9600 or more, and also preferably 0.9800 or more. The upper limit is not particularly limited, but is usually 1.0000 or less.
[0252] refer to Fig. 9 , the above Raman spectral characteristics are explained.
[0253] First, a Raman spectrum of the solid electrolyte (I) is obtained. As a method for measuring Raman spectra, Raman imaging is implemented. Raman imaging refers to microscopic spectroscopy combined with microscopy in Raman spectroscopy. Specifically, it is a method of detecting measurement light containing Raman scattered light by scanning excitation light on a sample, and visualizing the distribution of components based on the intensity of the measurement light.
[0254] The measurement conditions for Raman imaging are set as follows: at 27°C and in the atmosphere, the excitation light is 532nm, the objective lens is 100 times, the point scanning is in the mapping mode, the step size is 1μm, the exposure time for each point is 1 second, the accumulation and integration times are 1 time, and the measurement range is 70μm×50μm.
[0255] Furthermore, the Raman spectrum data is subjected to principal component analysis (PCA) processing to remove noise. Specifically, in the principal component analysis processing, the spectrum is reorganized using components having an autocorrelation coefficient of 0.6 or more.
[0256] exist Fig. 9 An example of the Raman spectrum of the solid electrolyte (I) is shown in FIG. Fig. 9 In the graph shown, the vertical axis represents the Raman intensity and the horizontal axis represents the Raman shift. Fig. 9 The Raman spectrum shown is 600-850 cm -1 The coefficient of determination (R 2 ). That is, in Fig. 9 The Raman spectrum of 600-850cm -1 In the wave number region, the regression line is obtained by the least square method ( Fig. 9 The bold line in the figure is used to calculate the coefficient of determination R of the regression line. 2 In addition, the coefficient of determination takes a value between 0 (no linear correlation) and 1 (complete linear correlation of the measured values) depending on the linear correlation of the measured values.
[0257] In the solid electrolyte (I), as Fig. 9 As shown, at 600-850cm -1 In the wavenumber region, almost no peak is observed, and as a result, a high determination coefficient is shown.
[0258] In addition, the above determination coefficient R 2 It is equivalent to the square of the correlation coefficient (Pearson product-moment correlation coefficient). More specifically, in this specification, the coefficient of determination R 2 The calculation is performed by the following formula: wherein x1 and y1 represent the wave number in the Raman spectrum and the Raman intensity corresponding to the wave number, x2 represents the (arithmetic) average of the wave number, and y2 represents the (arithmetic) average of the Raman intensity.
[0259] [Formula 8]
[0260]
[0261] On the other hand, for reference, Fig.10 The Raman spectrum of a typical lithium tetraborate crystal is shown in FIG. Fig.10 As shown, in the case of a conventional lithium tetraborate crystal, the wavelengths of 716 to 726 cm-1 are derived from its structure. -1 and 771~785cm -1 In the wave number region of 600-850 cm -1In the wave number region, when the coefficient of determination was calculated by linear regression analysis using the least squares method, the coefficient of determination was less than 0.9400.
[0262] That is, when the determination coefficient is 0.9400 or more, it means that the solid electrolyte (I) contains almost no crystal structure. Therefore, as a result, it is considered that the solid electrolyte (I) has the characteristics of being easy to plastically deform and Li + Excellent jumping properties.
[0263] (Infrared absorption spectrum characteristics)
[0264] When the solid electrolyte (I) contains at least water as bound water, in the infrared absorption spectrum, -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region (between 3000 and 3500 cm -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 The maximum absorption intensity in the wave number region of the wavelength region is preferably 1 / 5 or more (0.2 or more). Among them, the above ratio is preferably 3 / 10 or more, more preferably 2 / 5 or more. The upper limit is not particularly limited, but is preferably 1 or less.
[0265] In the infrared absorption spectrum, the range of 3000 to 3500 cm -1 The OH stretching vibration mode is observed in the wave number region of 800-1600 cm -1 The BO stretching vibration mode was observed in the wave number region of . In the solid electrolyte (I), a strong absorption intensity derived from the OH stretching vibration mode was observed, which indicates that a large number of OH groups and a large amount of water are contained. In this solid electrolyte (I), lithium ions become easy to move, and as a result, the ion conductivity tends to be improved.
[0266] In addition, at 800-1600cm -1 In the wave number region, vibration modes originating from lithium salts can also be observed.
[0267] The infrared absorption spectrum measurement conditions can be set as follows.
[0268] Objective lens: 32x Cassegrain (NA0.65), Detector: MCT-A, Measuring range: 650~4000cm -1 , Resolution: 4cm -1 , Sample cell: Use diamond cell for measurement.
[0269] The infrared absorption spectrum obtained was corrected to remove signals from water and CO 2 in the atmosphere, and the background was offset corrected so that the absorption intensity became 0. After vacuum drying at 40° C. for 2 hours, the spectrum was measured in the atmosphere.
[0270] The ion conductivity (27°C) of the solid electrolyte (I) is not particularly limited, but is preferably 1.0×10 -8 S / cm or more, more preferably 1.0×10 -7 S / cm or more. In addition, when the solid electrolyte (I) contains at least water as bound water, the ion conductivity (27°C) is preferably 1.0×10 -5 S / cm or more, more preferably 1.0×10 -4 S / cm or more, more preferably 1.0×10 -3 S / cm or more, particularly preferably 3.0×10 -3 S / cm or more. The upper limit is not particularly limited, but is often 1.0×10 -2 S / cm or less.
[0271] Furthermore, the solid electrolyte (I) also preferably exhibits the following characteristics or properties.
[0272] (Mass reduction rate)
[0273] When the solid electrolyte (I) contains at least water as bound water, the mass reduction rate when the solid electrolyte (I) is heated to 800° C. is preferably 20 to 40% by mass, more preferably 25 to 35% by mass. The mass reduction caused by the above heating is considered to be at least the removal of the water contained in the solid electrolyte (I). By containing such water, the solid electrolyte (I) can further improve the conductivity of lithium ions.
[0274] In the above-mentioned heating treatment, heating is performed at a temperature increase rate of 20°C / second within a range of 25°C to 800°C. When measuring the mass reduction, a known thermogravimetric differential thermal analysis (TG-DTA) device can be used. The above-mentioned mass reduction rate is calculated as follows:
[0275] {(mass at 25°C - mass at 800°C) / mass at 25°C}×100.
[0276] When measuring the mass reduction rate, the solid electrolyte (I) was previously vacuum dried at 40° C. for 2 hours. The mass reduction rate was measured in the atmosphere.
[0277] (Bulk elastic modulus)
[0278] The bulk modulus of the solid electrolyte (I) is not particularly limited, and is, for example, preferably 45 GPa or less, and more preferably 40 GPa or less. The lower limit is not particularly limited, but is preferably 5 GPa or more.
[0279] (Particle size)
[0280] The median particle size (D50) of the solid electrolyte (I) is not particularly limited, but is preferably 0.01 to 20 μm, and more preferably 0.1 to 2.0 μm.
[0281] The solid electrolyte layer constituting the secondary battery of the present invention may contain other components in addition to the solid electrolyte (I).
[0282] For example, the solid electrolyte layer may include a binder composed of an organic polymer. The organic polymer constituting the binder may be in a particle form or a non-particle form. By including the binder, cracks in the solid electrolyte layer or the electrode layer can be more reliably prevented when the battery is used as a wound secondary battery.
[0283] Furthermore, the solid electrolyte layer may include other solid electrolytes other than the solid electrolyte (I). Other solid electrolytes refer to solid electrolytes that enable lithium ions to move inside them. As solid electrolytes, inorganic solid electrolytes are preferred. As other solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes and hydride solid electrolytes can be cited. If safety is taken into account, at least one of oxide solid electrolytes, halide solid electrolytes and hydride solid electrolytes is preferred, and oxide solid electrolytes are more preferred.
[0284] In the solid electrolyte layer, the content of the solid electrolyte (I) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, also preferably 80 mass % or more, and even preferably 90 mass %.
[0285] The thickness of the solid electrolyte layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 1000 μm, preferably 50 to 400 μm.
[0286] <Positive electrode layer>
[0287] The positive electrode layer is usually composed of a positive electrode collector and a positive electrode active material layer, but when the positive electrode collector also functions as a positive electrode active material layer (in other words, when the positive electrode active material layer also functions as a positive electrode collector), it is not necessary to be composed of the two layers of the positive electrode collector and the positive electrode active material layer, and can be a single-layer structure. In addition, the positive electrode active material layer usually contains a solid electrolyte (preferably an inorganic solid electrolyte) together with the positive electrode active material, but may not contain a solid electrolyte. The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, also preferably 80% by mass or more, and also preferably 90% by mass.
[0288] When the positive electrode active material layer contains a solid electrolyte, the type of the solid electrolyte is not particularly limited. From the viewpoint of attaching importance to flexibility, a sulfide-based solid electrolyte can be used, and from the viewpoint of attaching importance to higher safety, an oxide-based solid electrolyte can be used.
[0289] From the viewpoint of achieving both flexibility and safety at a high level, it is preferred to use the above-mentioned solid electrolyte (I). In this way, the solid electrolyte (I) can also act as a binder to the solid particles contained in the positive electrode layer, thereby enabling the positive electrode layer to have higher flexibility. As a result, when manufacturing a wound lithium-ion secondary battery, when the positive electrode layer is wound, the generation of cracks can be effectively suppressed.
[0290] The positive electrode active material used in the positive electrode layer itself can be widely used from those that can be used in ordinary lithium ion secondary batteries. Preferred embodiments of the positive electrode active material will be described below.
[0291] (Positive electrode active material)
[0292] The positive electrode active material is preferably a positive electrode active material that can reversibly insert and / or release lithium ions. The positive electrode active material is not particularly limited, preferably a transition metal oxide, more preferably a transition metal oxide containing a transition metal element Ma (one or more elements selected from Co, Ni, Fe, Mn, Cu and V). In addition, the element Mb (metal elements of the 1st (Ia) group of the periodic table other than lithium, elements of the 2nd (IIa) group, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P and B, etc.) can be mixed in the transition metal oxide. As a mixed amount, it is preferably 0 to 30 mol% relative to the amount of the transition metal element Ma (100 mol%). More preferably, the material is synthesized by mixing in a manner such that the molar ratio of Li / Ma is 0.3 to 2.2.
[0293] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) transition metal phosphate compounds containing lithium, (MD) transition metal halophosphate compounds containing lithium, and (ME) transition metal silicate compounds containing lithium. Among them, (MA) transition metal oxides having a layered rock salt structure are preferred, and LiCoO2 or LiNi2O3 are more preferred. 1 / 3 Co 1 / 3 Mn 1 / 3 O2.
[0294] Examples of the transition metal oxide (MA) having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNiO2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0295] Examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiNi 0.5 Mn 1.5 O4([LNMO]), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0296] As (MC) transition metal phosphate compounds containing lithium, for example, there can be mentioned olivine-type iron phosphate salts such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphate iron salts such as Li2CoP2O7(LCP) and LiFeP2O7, cobalt phosphate salts such as LiCoPO4, and monoclinic NASICON-type vanadium phosphate salts such as Li3V2(PO4)3 (lithium vanadium phosphate).
[0297] Examples of the lithium-containing transition metal halophosphate compound (MD) include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0298] Examples of the (ME) lithium-containing transition metal silicate compound include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .
[0299] The shape of the positive electrode active material is not particularly limited, and is usually in the form of particles. The volume average particle size of the positive electrode active material is not particularly limited, and is preferably 0.1 to 50 μm, for example. The volume average particle size of the positive electrode active material particles can be determined in the same manner as the volume average particle size of the negative electrode active material described later.
[0300] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0301] The positive electrode active material may be surface-coated with a surface coating agent, sulfur or phosphorus, which will be described later, in the same manner as the negative electrode active material, which will be described later, or with active light.
[0302] The positive electrode active material may be used alone or in combination of two or more.
[0303] (Positive electrode collector)
[0304] The current collector constituting the positive electrode layer is an electron conductor and is usually in the form of a thin film sheet.
[0305] As the constituent material of the positive electrode collector, aluminum, aluminum alloy, stainless steel, nickel and titanium can be cited, preferably aluminum or aluminum alloy. In addition, as the positive electrode collector, a positive electrode collector (forming a thin film) treated with carbon, nickel, titanium or silver on the surface of aluminum or stainless steel can also be cited.
[0306] The thickness of the positive electrode active material layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 500 μm, preferably 20 to 200 μm.
[0307] The thickness of the positive electrode current collector constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 100 μm, preferably 10 to 50 μm.
[0308] <Negative electrode layer>
[0309] The negative electrode layer is usually composed of a negative electrode collector and a negative electrode active material layer, but when the negative electrode collector also functions as a negative electrode active material layer (in other words, when the negative electrode active material layer also functions as a negative electrode collector), it is not necessary to be composed of the two layers of the negative electrode collector and the negative electrode active material layer, and can be a single-layer structure. In addition, the negative electrode active material layer usually contains a solid electrolyte (preferably an inorganic solid electrolyte) together with the negative electrode active material, but it may not contain a solid electrolyte. The content of the negative electrode active material in the negative electrode active material layer is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, also preferably 80% by mass or more, and also preferably 90% by mass.
[0310] When the negative electrode active material layer contains a solid electrolyte, the type of the solid electrolyte is not particularly limited. From the viewpoint of attaching importance to flexibility, a sulfide-based solid electrolyte can be used, and from the viewpoint of attaching importance to higher safety, an oxide-based solid electrolyte can be used.
[0311] From the viewpoint of achieving both flexibility and safety at a high level, it is preferred to use the above-mentioned solid electrolyte (I). In this way, the solid electrolyte (I) can also act as a binder to the solid particles contained in the negative electrode layer, thereby making the negative electrode layer have higher flexibility. As a result, when manufacturing a wound lithium-ion secondary battery, when the negative electrode layer is wound, the generation of cracks can be effectively suppressed.
[0312] The negative electrode active material used in the negative electrode layer itself can be widely used from those that can be used in ordinary lithium ion secondary batteries. Preferred embodiments of the negative electrode active material will be described below.
[0313] (Negative electrode active material)
[0314] The negative electrode active material is preferably a negative electrode active material that can reversibly insert and release lithium ions. The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials, oxides of metal or semimetal elements, lithium monomers, lithium alloys, and negative electrode active materials that can form alloys with lithium.
[0315] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon, for example, carbonaceous materials made of various synthetic resins such as calcined petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and PAN (polyacrylonitrile) resin or furfuryl alcohol resin.
[0316] In addition, various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as intermediate phase microspheres, graphite whiskers, and flat graphite can also be cited.
[0317] These carbonaceous materials can be further divided into hardly graphitizable carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization.
[0318] Furthermore, the carbonaceous material preferably has the interplanar spacing, density or crystallite size described in Japanese Patent Laid-Open No. 62-022066, Japanese Patent Laid-Open No. 2-006856 and Japanese Patent Laid-Open No. 3-045473. The carbonaceous material need not be a single material, and a mixture of natural graphite and artificial graphite described in Japanese Patent Laid-Open No. 5-090844 and graphite with a coating layer described in Japanese Patent Laid-Open No. 6-004516 can also be used.
[0319] As the carbonaceous material, hard carbon or graphite is preferred, and graphite is more preferred.
[0320] The oxide of the metal element or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements, composite oxides of metal elements and semi-metal elements, and oxides of semi-metal elements (semi-metal oxides). In addition, composite oxides of metal elements and composite oxides of metal elements and semi-metal elements are collectively referred to as metal composite oxides.
[0321] As these oxides, iron oxides such as Fe 3 O 4 are preferred, and amorphous oxides are also preferred. Furthermore, chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table are also preferred.
[0322] In the present invention, semi-metallic elements refer to elements showing properties between metal elements and non-metallic elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and also include three elements of selenium, polonium and astatine.
[0323] Furthermore, amorphous means that, by X-ray diffraction using CuKα rays, a broad scattering band having a vertex in a region of 20 to 40° in 2θ values may also have crystalline diffraction lines. It is preferred that the strongest intensity of the crystalline diffraction lines seen in a region of 40 to 70° in 2θ values is 100 times or less, more preferably 5 times or less, and further preferably a diffraction line having no crystalline diffraction line intensity at the vertex of the broad scattering band seen in a region of 20 to 40° in 2θ values.
[0324] Among the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides consisting of a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi) are further preferred.
[0325] As amorphous oxides and chalcogenides, preferred are Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 or Sb2S5.
[0326] As the negative electrode active material that can be used together with the amorphous oxide negative electrode active material centered on Sn, Si or Ge, carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, or negative electrode active materials that can alloy with lithium are preferred.
[0327] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal element or a semi-metal element (particularly a metal (complex) oxide) and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component.
[0328] Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above-mentioned metal oxides, the above-mentioned metal composite oxides or the above-mentioned chalcogenides. More specifically, Li2SnO2 is included.
[0329] The negative electrode active material (e.g., metal oxide) also preferably contains titanium (titanium oxide). Specifically, since the volume change when absorbing and releasing lithium ions is small, the rapid charge and discharge characteristics are excellent. From the perspective of being able to increase the life of the all-solid-state lithium ion secondary battery that suppresses electrode degradation, Li4Ti5O is preferred. 12 (lithium titanate [LTO]).
[0330] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for all-solid-state lithium ion secondary batteries, and examples thereof include lithium aluminum alloys.
[0331] The negative electrode active material capable of forming an alloy with lithium is not particularly limited as long as it is a material commonly used as a negative electrode active material for an all-solid-state lithium-ion secondary battery. As the above-mentioned negative electrode active material, negative electrode active materials (alloys) containing silicon or tin elements and metals such as Al and In can be cited, preferably negative electrode active materials containing silicon elements (active materials containing silicon elements) that can achieve higher battery capacity, and more preferably active materials containing silicon elements with a silicon content of more than 50 mol% of all constituent elements.
[0332] Generally, a negative electrode containing these negative electrode active materials (for example, an Si negative electrode containing an active material containing a silicon element, an Sn negative electrode containing an active material containing a tin element) can occlude more Li ions compared to a carbon negative electrode (such as graphite and acetylene black). That is, the occluding amount of Li ions per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0333] As the active material containing a silicon element, for example, silicon materials such as Si and SiOx (0 < x ≤ 1) can be cited. Further, silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper or lanthanum (for example, LaSi2, VSi2, La-Si, Gd-Si and Ni-Si) or organized active materials (for example, LaSi2 / Si) can be cited. In addition, active materials containing a silicon element and a tin element such as SnSiO3 and SnSiS3 can be cited. Further, regarding SiOx, it can be used as a negative electrode active material (semi-metal oxide) itself, and since Si is generated by the operation of a all-solid-state lithium ion secondary battery, it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.
[0334] As the negative electrode active material having a tin element, for example, those containing Sn, SnO, SnO2, SnS, SnS2 and the above-mentioned active materials containing a silicon element and a tin element can be cited.
[0335] From the viewpoint of battery capacity, as the negative electrode active material, a negative electrode active material that can be alloyed with lithium is preferred, more preferably the above-mentioned silicon materials or silicon-containing alloys (alloys containing a silicon element), and further preferably silicon (Si) or a silicon-containing alloy.
[0336] As the negative electrode active material, it is also preferable to use a titanium niobium composite oxide. The theoretical volume capacity density of the titanium niobium composite oxide is high, and it can be expected to have a long life and also be capable of rapid charging. As the titanium niobium composite oxide, for example, TiNb2O7 etc. can be cited.
[0337] The shape of the negative electrode active material is not particularly limited, but particle shape is preferred. The volume average particle diameter of the negative electrode active material is not particularly limited, but is preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and further preferably 1.0 to 15 μm.
[0338] The measurement of the volume average particle diameter is carried out by the following steps.
[0339] Use water (heptane in the case of unstable substances in water) to dilute the negative electrode active material in a 20 mL sample bottle to prepare a 1% dispersion. The diluted dispersion sample was irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample and using a laser diffraction / scattering particle size distribution measuring device, 50 data readings were performed using a measuring quartz cell at a temperature of 25°C to obtain the volume average particle size. For other detailed conditions, refer to JIS Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Make 5 samples for each level and use their average value.
[0340] The negative electrode active material may be used alone or in combination of two or more.
[0341] The surface of the negative electrode active material may also be coated with another metal oxide.
[0342] As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, titanate spinel, tantalum oxides, niobium oxides and lithium niobate compounds can be cited, for example, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3 and Li3AlF6.
[0343] Furthermore, the surface of the electrode including the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0344] Furthermore, the surface of the negative electrode active material particles may be subjected to a surface treatment using active light or active gas (for example, plasma) before or after the surface is coated.
[0345] (Negative electrode current collector)
[0346] The current collector constituting the negative electrode layer is an electron conductor and is usually in the form of a thin film sheet.
[0347] As the constituent material of the negative electrode collector, aluminum, copper, copper alloy, stainless steel, nickel and titanium can be enumerated, preferably aluminum, copper, copper alloy or stainless steel. In addition, as the negative electrode collector, a negative electrode collector treated with carbon, nickel, titanium or silver on the surface of aluminum, copper, copper alloy or stainless steel can also be enumerated.
[0348] The thickness of the negative electrode active material layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 500 μm, preferably 20 to 200 μm.
[0349] The thickness of the negative electrode current collector constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 100 μm, preferably 10 to 50 μm.
[0350] The positive electrode layer and the negative electrode layer may contain components (other components) other than the solid electrolyte and the active material in their active material layers. For example, a conductive auxiliary agent may be contained.
[0351] As the conductive auxiliary agent, a substance generally known as a conductive auxiliary agent can be used. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electron conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.
[0352] In addition to the above-mentioned conductive additives, a common conductive additive containing no carbon atoms, such as metal powder or metal fiber, can be used.
[0353] A conductive aid is an aid that does not insert or release Li during battery charge and discharge and does not function as an active material. Therefore, among conductive aids, substances that function as active materials in the active material layer during battery charge and discharge are also classified as active materials rather than conductive aids. Whether or not a conductive aid functions as an active material during battery charge and discharge is not unique, but is determined by the combination with the active material.
[0354] As other components, the above-mentioned binder and lithium salt can be mentioned.
[0355] <Separator layer>
[0356] In the present invention, the separator layer is a layer used for insulation between collectors in a wound secondary battery. Therefore, as long as it is an insulating film, there is no particular limitation, and separators generally used for insulation between collectors can be widely used. The thickness of the separator layer is also not particularly limited, and can be set to 10 to 100 μm, for example. As an insulating film, for example, a fluororesin film can be cited.
[0357] <Manufacturing of wound-type all-solid-state lithium-ion secondary batteries>
[0358] The secondary battery of the present invention uses a solid electrolyte (I) at least in the solid electrolyte layer, and can be manufactured by referring to the conventional method for manufacturing a wound all-solid-state secondary battery. That is, the method for manufacturing a secondary battery of the present invention includes the step of winding a laminated body formed by sequentially configuring a positive electrode layer, a solid electrolyte layer, and a negative electrode layer on a core material.
[0359] For example, a positive electrode forming composition (slurry) containing a positive electrode active material is applied to a metal foil as a positive electrode collector to form a positive electrode active material layer, and then a solid electrolyte layer-forming dispersion (slurry) containing a solid electrolyte is applied to the positive electrode active material layer to form a solid electrolyte layer, and further, a negative electrode forming composition (slurry) containing a negative electrode active material is applied to the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode collector (metal foil) is overlapped on the negative electrode active material layer. In addition, a separator layer is arranged on the outside of the positive electrode collector and / or the negative electrode collector as needed. The whole can be pressurized, and the obtained laminated body can be wound on a core material to obtain a Figure 2 The wound-type all-solid-state lithium-ion secondary battery shown.
[0360] Furthermore, it is also possible to reverse the formation method of each layer, form a negative electrode active material layer, a solid electrolyte layer and a positive electrode active material layer on the negative electrode collector, and overlap the positive electrode collector, and, as required, configure a separator layer on the outside of the positive electrode collector and / or the negative electrode collector. It is also possible to pressurize the entirety, and wind the obtained laminate on a core material, thereby manufacturing a wound-type all-solid-state lithium-ion secondary battery.
[0361] As another method, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer are separately prepared and stacked, and a separator layer is arranged on the outside of the positive electrode collector and / or the negative electrode collector as required. It is also possible to pressurize as required and wind the obtained stacked body on a core material to manufacture a wound-type all-solid-state lithium-ion secondary battery.
[0362] In this case, in the formation of each layer, a support such as a nonwoven fabric may be disposed as necessary so that each layer becomes a self-supporting film.
[0363] The direction in which the laminate is wound on the core material is not particularly limited, and the laminate may be wound with the positive electrode side inside and the negative electrode side outside, or with the negative electrode side inside and the positive electrode side outside.
[0364] In the manufacture of the secondary battery of the present invention, even if a sulfide-based solid electrolyte is not used as a solid electrolyte, the above-mentioned solid electrolyte (I) of the oxide system that can be easily plastically deformed under pressure can also suppress the formation of a layer of interface resistance between solid particles or between layers. Therefore, even if a secondary battery is manufactured in the presence of moisture (for example, under the atmosphere), the generation of harmful substances such as hydrogen sulfide can be avoided, and the productivity is excellent. In addition, manufacturing a secondary battery in the presence of moisture refers to manufacturing the secondary battery of the present invention under the condition that the solid electrolyte layer is in contact with moisture (for example, under the atmosphere). Typically, the formation of a laminated body including a solid electrolyte layer formed in the secondary battery of the present invention under the condition that moisture is in contact with the solid electrolyte layer (for example, under the atmosphere) can be cited.
[0365] Furthermore, the solid electrolyte (I) itself is soft and can be plastically deformed, and its function is similar to that of a binder, which helps to improve the adhesion between solid particles and between layers. Therefore, it is also possible to form layers without using a binder such as an organic polymer.
[0366] The secondary battery of the present invention is preferably initialized after production or before use.
[0367] <Applications of wound-type all-solid-state lithium-ion secondary batteries>
[0368] The secondary battery of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a video movie, a liquid crystal television, a handheld cleaner, a portable CD player, a mini disc player, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio and a backup power supply can be cited. As other consumer products, automobiles, electric vehicles, motors, lighting equipment, toys, game consoles, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used for various military purposes and space purposes. And, it can also be combined with solar cells.
[0369] Example
[0370] The present invention will be described in further detail based on the examples, but the present invention is not limited thereto. The production of the solid electrolyte or the production of the secondary battery described below is performed in an atmosphere in which moisture exists.
[0371] [Reference Example 1]
[0372] <Preparation of solid electrolyte (I)>
[0373] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) were ball-milled under the following conditions: pot: yttria-stabilized zirconia (YSZ) (45 ml), grinding balls: YSZ (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder amount: 1 g, atmosphere: air, ball mill processing time: 100 hours, thereby obtaining a micronized lithium-containing oxide (hereinafter also referred to as "micronized lithium-containing oxide").
[0374] To 1.0 g of the obtained lithium oxide-containing fine material, 0.02 g of LiFSI (chemical formula: Li(FSO2)2N) was added as a lithium salt (2 mass % relative to the lithium oxide-containing fine material), and ball milling was performed for 100 hours to obtain a powdered solid electrolyte (I)-1.
[0375] In addition, the molar ratio of the lithium-containing oxide to the lithium salt in the solid electrolyte shown in the following table was calculated based on the charged amounts.
[0376] The elemental analysis of the obtained powdered solid electrolyte (I)-1 revealed that the composition of the solid electrolyte (I)-1 was Li 1.98 B 4.00 O 6.83 F 0.08 S 0.07 N 0.04 In addition, among the elements contained in the solid electrolyte (I), Li and B were analyzed by ICP-OES, F and S were analyzed by combustion ion chromatography, and N was analyzed by inert gas fusion method. For O, the analyzed masses of the elements other than O were added and calculated as a difference from the total amount of powder.
[0377] <Production and evaluation of solid electrolyte molded body>
[0378] The powdered solid electrolyte (I)-1 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte molded body (compressed powder body 1). The shape of the compressed powder body 1 was a cylinder with a diameter of 10 mm and a thickness of 0.5 to 1 mm. The ion conductivity of the compressed powder body 1 was measured and the ion conductivity of the compressed powder body 1 was 2.8×10 -7 S / cm, and 1.6×10-6 S / cm.
[0379] The ionic conductivity of the above-mentioned solid electrolyte (I)-1 was calculated by the following method: electrodes consisting of two In foils were arranged in a manner of clamping the powder compact 1, and the AC impedance between the two In electrodes was measured in the measurement frequency range of 1 Hz to 1 MHz at a measurement temperature of 27°C or 60°C and an applied voltage of 100 mV, and the arc diameter of the obtained Cole-Cole diagram was analyzed.
[0380] The particle size distribution of the solid electrolyte (I)-1 obtained above is about several hundred nm to 10 μm, the average particle size is 1.6 μm, and the median particle size (D50) is 1.5 μm. The particle size distribution of the solid electrolyte is obtained by obtaining a particle image by flow particle image analysis, and a histogram (particle size distribution) of the particle size of the solid electrolyte is prepared and calculated. The above particle size is equivalent to the equivalent circle diameter.
[0381] The bulk modulus of the solid electrolyte (I)-1 obtained in the above is 36GPa. In addition, the bulk modulus of the LBO powder before ball milling is 47GPa. The measurement of the bulk modulus of the solid electrolyte is implemented by ultrasonic attenuation method. Specifically, first, a suspension obtained by suspending the solid electrolyte in pure water is made. The content of the solid electrolyte in the suspension is set to 1.2 mass % relative to the total mass of the suspension. Then, the ultrasonic attenuation spectrum of the above suspension is measured, and the bulk modulus (GPa) of the solid electrolyte is obtained according to the fitting based on the scattering attenuation theoretical formula. In addition, when calculating the bulk modulus, the density of the solid electrolyte is set to 2.3g / mL, and Poisson's ratio is set to 0.12 and fitted. In addition, regarding the fitting based on the above-mentioned scattering attenuation theoretical formula, the bulk elastic modulus was calculated using equations (7), (12) and (13) described in Kohjiro Kubo et al., Ultrasonics 62 (2015) pp. 186-194.
[0382] The solid electrolyte (I)-1 obtained in the above was used and the solid electrolyte (I)-1 was measured by SPring-8BL04B2 (accelerating voltage: 61.4 keV, wavelength: ) was used for total X-ray scattering measurement. The sample was sealed in a 2 mmφ or 1 mmφ Kapton capillary and the experiment was performed under vacuum. As described above, the obtained data was Fourier transformed to obtain the reduced two-body distribution function G(r). Fig.11 The reduced dimer distribution function G(r) obtained from solid electrolyte (I)-1 is shown in FIG.
[0383] As a result of the analysis, it was confirmed that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, when r is In the range of , the peak G(r) shows more than 1.0, and the peak is located at The first peak and the peak G(r) show more than 1.0, and the peak is located at The second peak of the reduced two-body distribution function G(r) is confirmed when r exceeds and The absolute value of G(r) in the following range is less than 1.0.
[0384] In the reduced two-body distribution function G(r), when r is greater than and The absolute value of G(r) in the following range is less than 1.0, so it can be seen that in the solid electrolyte (I) obtained above, there is almost no long-range order, and the solid electrolyte (I)-1 is in an amorphous state. On the other hand, in the solid electrolyte (I)-1, the peaks attributed to the BO distance and the BB distance observed in the conventional lithium tetraborate crystal are maintained. Since the conventional lithium tetraborate crystal has a structure (diborate structure) in which BO4 tetrahedrons and BO3 triangles exist in 1:1, it is inferred that in the above-mentioned solid electrolyte (I)-1, its structure is maintained.
[0385] The solid electrolyte (I)-1 was solidified at 20°C and 120°C respectively. 7 Li-NMR measurement, the half-maximum full width (half-maximum full width 1) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 20°C and the half-maximum full width (half-maximum full width 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 120°C are obtained. Based on the obtained half-maximum full width 1 and half-maximum full width 2, the percentage of the half-maximum full width 2 relative to the half-maximum full width 1 {(half-maximum full width 2 / half-maximum full width 1) × 100}, that is, the half-maximum full width ratio (%) of the solid electrolyte (I) is 65%.
[0386] Raman imaging measurement was performed on the powder compact 1. The measurement conditions were as follows: excitation light of 532 nm, objective lens of 100 times, point scanning in mapping mode, 1 μm step length, exposure time of 1 second per point, accumulation and integration times of 1 time, and measurement range of 70 μm×50 μm. Noise was removed from the obtained data by PCA processing.
[0387] In the Raman spectrum obtained in this way, the -1The coefficient of determination was obtained by performing linear regression analysis by the least square method in the wave number region. The coefficient of determination of the obtained powder compact 1 was 0.9952.
[0388] [Reference Example 2]
[0389] A powdered solid electrolyte (I)-2 was prepared in the same manner as in Reference Example 1 except that 0.05 g of LiFSI was added as a lithium salt to 1.0 g of the fine material containing lithium oxide prepared in Reference Example 1 (5% by mass relative to the fine material containing lithium oxide). The result of elemental analysis showed that the composition of the obtained solid electrolyte (I)-2 was Li 2.01 B 4.00 O 7.47 F 0.12 S 0.12 N 0.07 .
[0390] Next, the powdered solid electrolyte (I)-2 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte molded body (compressed powder body 2) identical to Reference Example 1. The ion conductivity of the obtained compressed powder body 2 at 27°C was 3.0×10 -7 S / cm, and 1.7×10 -6 S / cm.
[0391] [Reference Example 3]
[0392] A powdered solid electrolyte (I)-3 was prepared in the same manner as in Reference Example 1 except that 0.05 g of lithium iodide (LiI) was added as a lithium salt to 1.0 g of the lithium oxide-containing fine substance prepared in Reference Example 1 (5% by mass relative to the lithium oxide-containing fine substance). The result of elemental analysis showed that the composition of the obtained solid electrolyte (I)-3 was Li 2.05 B 4.00 O 9.28 I 0.07 In addition, elemental analysis of iodine was performed by burning IC.
[0393] Next, the powdered solid electrolyte (I)-3 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte compact (compressed powder 3). The ion conductivity of the obtained compressed powder 3 at 27°C was 3.1×10 -5 S / cm, and 9.4×10 -5 S / cm.
[0394] [Reference Example 4]
[0395] A powdered solid electrolyte (I)-4 was prepared in the same manner as in Reference Example 1 except that 0.02 g of lithium chloride (LiCl) was added as a lithium salt to 1.0 g of the lithium oxide-containing fine substance used in Reference Example 1 (2 mass % relative to the lithium oxide-containing fine substance). The result of elemental analysis showed that the composition of the obtained solid electrolyte (I)-4 was Li 2.03 B 4.00 O 9.80 Cl 0.06 In addition, elemental analysis of chlorine was performed by burning IC.
[0396] Next, the powdered solid electrolyte (I)-4 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte compact (compressed powder 4). The ion conductivity of the obtained compressed powder 4 at 27°C was 2.3×10 -5 S / cm, and 3.6×10 at 60°C -5 S / cm.
[0397] [Comparative Reference Example 1]
[0398] The elemental analysis of the LBO powder (Li2B4O7 crystals in powder form without ball milling) used in Reference Example 1 showed that the composition of the LBO powder obtained was Li 1.96 B 4.00 O 6.80 The LBO powder was compacted at 27° C. (room temperature) at an effective pressure of 220 MPa to obtain a comparative powder compact C1. The ion conductivity of the obtained powder compact C1 could not be detected.
[0399] And, in the same manner as in Reference Example 1, total X-ray scattering measurement was performed using LBO powder, thereby obtaining the reduced two-body distribution function G(r). Fig.12 The reduced two-body distribution function G(r) obtained from total X-ray scattering measurements is shown in FIG.
[0400] The analysis results show that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of LBO powder, there is a peak located at The first peak (corresponding to the vicinity of BO) and the peak are located at The second peak of the BB (corresponding to the BB), the peak G (r) of the first peak and the second peak is greater than 1.0 (reference Fig.12 ). In addition, there is a peak located at and The absolute value of the peak G(r) of each peak obviously exceeds 1.0 (ref. Fig.12 ).
[0401] [Comparative Reference Example 2]
[0402] The result of elemental analysis of the fine material containing lithium oxide prepared in Reference Example 1 (the material obtained by ball milling powdered Li2B4O7 crystals) showed that the composition of the fine material containing lithium oxide was Li 1.94 B 4.00 O 6.80 .
[0403] Next, the lithium oxide-containing fine material was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a reference powder compact (powder compact R1). The ion conductivity of the obtained powder compact R1 at 27°C was 7.5×10 -9 S / cm, and 7.5×10 at 60°C -8 S / cm.
[0404] The particle size distribution of the solid electrolytes (I)-2, (I)-3 and (I)-4 obtained in Reference Examples 2 to 4 and the fine material containing lithium oxide of Comparative Reference Example 2 is about several hundred nm to 10 μm, the average particle size is about 1.6 μm, and the median particle size (D50) is about 1.5 μm. In addition, for the solid electrolytes (I)-2, (I)-3 and (I)-4 obtained in Reference Examples 2 to 4, the LBO powder used in Comparative Reference Example 1, and the fine material containing lithium oxide used in Comparative Reference Example 2, the bulk elastic modulus, the reduction two-body distribution function G (r) and the ratio of the half-maximum full width 2 to the half-maximum full width 1 were respectively determined in the same manner as in Reference Example 1. In addition, for each of the pressed powders obtained in Reference Examples 2 to 4 and Comparative Reference Examples 1 and 2, the determination coefficient was determined in the same manner as in Reference Example 1. The evaluation results based on each measurement are summarized in Table 1-1, Table 1-2 and Table 2.
[0405] In Table 2, in the column of "Requirement A-1", the case where requirement A-1 is satisfied is indicated as "A", and the case where requirement A-1 is not satisfied is indicated as "B". Furthermore, in the column of "Requirement A-2", the case where requirement A-2 is satisfied is indicated as "A", and the case where requirement A-2 is not satisfied is indicated as "B".
[0406] In Table 2, "full width at half maximum ratio (%)" and "coefficient of determination" are the same as those described in the above description of Reference Example 1.
[0407] [Table 1-1]
[0408]
[0409] [Table 1-2]
[0410]
[0411] [Table 2]
[0412]
[0413] As shown in the above table, it can be seen that the solid electrolytes of Reference Examples 1 to 4 have excellent ion conductivity compared with the LBO powder (Li2B4O7 crystals) of Comparative Reference Example 1, and compared with the fine lithium oxide-containing material (the material obtained by ball milling powdered Li2B4O7 crystals) of Comparative Reference Example 2.
[0414] (X-ray diffraction measurement)
[0415] Using CuKα rays, X-ray diffraction measurements were performed on the solid electrolyte (I)-2 prepared in Reference Example 2 and the LBO powder used in Comparative Reference Example 1. The measurement conditions were 0.01° / step and 3° / minute.
[0416] exist Fig.13 , the X-ray diffraction pattern of the LBO powder of Comparative Reference Example 1 is shown. Fig.13 As shown, in the LBO powder used in the comparative reference example 1, multiple peaks with small widths were observed. More specifically, the strongest peak corresponding to the (1, 1, 2) plane was observed at a position with a 2θ value of 21.78°. As other major diffraction peaks, a peak corresponding to the (2, 0, 2) plane was shown at a position of 25.54°, a peak corresponding to the (2, 1, 3) plane was shown at a position of 33.58°, and a peak corresponding to the (3, 1, 2) plane was shown at a position of 34.62°, and the intensities of these three peaks were roughly the same. These peaks originate from the crystal components.
[0417] exist Fig.14 In the figure, the X-ray diffraction pattern of solid electrolyte (I)-2 is shown. Fig.14 As shown, solid electrolyte (I)-2 exhibits the above-mentioned desired X-ray diffraction characteristics. Fig.13 In the figure, it can be seen that the existing crystalline components are amorphized by mechanical grinding, and the sharp peaks derived from lithium tetraborate crystals disappear and become broadened. X-ray diffraction measurements were also performed on the solid electrolytes (I)-1, (I)-3 and (I)-4 prepared in Reference Examples 1, 3 and 4. The results showed that they showed the above-mentioned desired X-ray diffraction characteristics and were in an amorphous state in the same manner as the solid electrolyte (I)-2.
[0418] [Reference Example 5]
[0419] To 1 g of the fine material containing lithium oxide used in Reference Example 1, 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added as a lithium salt (5% by mass relative to the fine material containing lithium oxide), and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration was 42% by mass, and ultrasonic dispersion was performed for 30 minutes. Then, the obtained dispersion was transferred to a glass petri dish and dried at 120°C for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Then, the obtained film was peeled off to obtain a powdery solid electrolyte (I)-5.
[0420] The X-ray diffraction measurement of the solid electrolyte (I)-5 was performed using CuKα radiation. The measurement conditions were set to 0.01° / step and 3° / minute. The results showed that the above-mentioned X-ray diffraction characteristics were satisfied, which showed that the solid electrolyte (I)-5 was in an amorphous state.
[0421] The solid electrolyte (I)-5 obtained in the above was used and the solid electrolyte (I)-5 was prepared by SPring-8L04B2 (accelerating voltage: 61.4 keV, wavelength: ) Total X-ray scattering measurements were performed. The samples were sealed in a 2 mm φ or 1 mm φ Kapton capillary and the experiment was performed. As described above, the obtained data were Fourier transformed to obtain the reduced two-body distribution function.
[0422] As a result of the analysis, it was confirmed that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, when r is The peak G(r) is greater than 1.0 and the peak is located at The first peak and the peak top G(r) show more than 1.0, and the peak top is located at The second peak of
[0423] On the other hand, in solid electrolyte (I)-5, the peaks attributed to the BO distance and BB distance observed in ordinary lithium tetraborate crystals are maintained. Ordinary lithium tetraborate crystals have a structure (diborate structure) in which BO4 tetrahedrons and BO3 triangles exist in a 1:1 ratio, and it is inferred that in solid electrolyte (I)-5, its structure is maintained.
[0424] Solid electrolyte (I)-5 was prepared at 120 °C. 7 The full width at half maximum (FWHM 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is relative to the solid electrolyte (I)-5 obtained above at 20°C. 7The ratio of the full width at half maximum (FWHM 1) of the peak whose chemical shift appeared in the range of -100 to +100 ppm in the spectrum obtained in Li-NMR measurement {(FWHM 2 / FWHM 1)×100} was 33%.
[0425] Will be solid at 20℃ 7 When the waveform of the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is separated, a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of less than 5 ppm is obtained, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 4%.
[0426] The solid electrolyte (I)-5 obtained in the above-mentioned manner was used and infrared absorption spectrum was measured under the above-mentioned conditions. In the infrared absorption spectrum obtained, the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wavenumber region is 0.72.
[0427] In the Raman spectrum of the solid electrolyte (I)-5 obtained above, the -1 The coefficient of determination obtained by least squares linear regression analysis in the wavenumber region is 0.9974.
[0428] As described above, the mass reduction rate of the solid electrolyte (I)-5 when heated from 25°C to 800°C was 29.8%.
[0429] Regarding the analysis of each element in the obtained solid electrolyte (I)-5, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC), and regarding N, the analysis mass of sulfur was estimated in consideration of each atomic weight in the Li salt, and regarding O, the analysis mass of the elements other than O was added and calculated as a difference from the total amount of powder. The results are shown in the following table.
[0430] [Reference Example 6]
[0431] 1 g of the lithium oxide-containing fine substance used in Reference Example 1 was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic dispersion was performed for 30 minutes. 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added to the obtained dispersion as a lithium salt (5 mass % relative to the lithium oxide-containing fine substance), and ultrasonic dispersion was performed for 30 minutes.
[0432] The obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Next, the obtained thin film was peeled off to obtain a powdered solid electrolyte (I)-6. Regarding the solid electrolyte (I)-6, various evaluations were performed in the atmosphere in the same manner as in Reference Example 5. The results are summarized in the following table.
[0433] [Reference Example 7]
[0434] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), powdered Li2B4O7 (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) was ball milled under the conditions of pot: YSZ (45 ml), grinding balls: YSZ (average particle size: 5 mm, weight: 70 g), rotation speed: 530 rpm (revolutions per minute), LBO powder amount: 4.2 g, atmosphere: air, and ball mill processing time: 100 hours to obtain a fine substance containing lithium oxide.
[0435] The obtained lithium oxide-containing fine substance was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a dispersion liquid 1.
[0436] Next, 3.25 g of LiFSI (chemical formula: Li(FSO 2 ) 2N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 2 .
[0437] The obtained dispersion 1 and solution 2 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-7. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-7 in the same manner as in Reference Example 5. The results are summarized in the following table.
[0438] [Reference Example 8]
[0439] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 7, Dispersion Liquid 3 was obtained.
[0440] Next, 2.32 g of LiFSI (chemical formula: Li(FSO 2 ) 2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 4 .
[0441] The obtained dispersion 3 and solution 4 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-8. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-8 in the same manner as in Reference Example 5. The results are summarized in the following table.
[0442] [Reference Example 9]
[0443] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 7, Dispersion Liquid 5 was obtained.
[0444] Next, 4.65 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 6 .
[0445] The obtained dispersion 5 and solution 6 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-9. The obtained powder was immediately subjected to various evaluations in the same manner as in Reference Example 5 under the atmosphere. The results are summarized in the following table.
[0446] [Reference Example 10]
[0447] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 7, Dispersion Liquid 7 was obtained.
[0448] Next, 7.13 g of LiTFSI (chemical formula: Li(F3CSO2)2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 8.
[0449] The obtained dispersion 7 and solution 8 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-10. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-10 in the same manner as in Reference Example 5. The results are summarized in the following table.
[0450] In Reference Example 10, the carbon contents shown in Table 3 below were estimated from the analyzed mass of sulfur in consideration of the atomic weights of the lithium salt.
[0451] [Comparative Reference Example 3]
[0452] In the same manner as in Comparative Reference Example 1, various evaluations were carried out in the same manner as in Reference Example 5 using LBO powder as Comparative Reference Example 3.
[0453] [Comparative Reference Example 4]
[0454] In the same manner as in Comparative Reference Example 2, various evaluations were carried out in the same manner as in Reference Example 5, except that a fine material containing lithium oxide was used as Comparative Reference Example 4.
[0455] In the following table, as described above, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, there is a peak located at r The first peak and the peak top in the range of r are If the peak G(r) of the first peak and the peak G(r) of the second peak show a value greater than 1.0, the "Short-range G(r)" column is set to "A", and all other cases are set to "B".
[0456] In Reference Examples 5 to 8 and Reference Examples 13 to 16 shown in the following table, the value of the peak top G(r) of the first peak was 1.2 or more.
[0457] Furthermore, in the above-mentioned reduced two-body distribution function G(r), when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, the "Long-range G(r)" column in the following table is set to "A", and when the absolute value of G(r) does not satisfy less than 1.0, it is set to "B".
[0458] In addition, the result of the X-ray diffraction measurement using the above-mentioned CuKα ray is set as "A" when the above-mentioned X-ray diffraction characteristics are satisfied, and "B" when the above-mentioned X-ray diffraction characteristics are not satisfied. In addition, in Reference Examples 5 to 10 and Reference Examples 11 to 17 shown in the following table, in the X-ray diffraction spectrum, the first peak, the second peak, the third peak, and the fourth peak are not present, or the intensity ratio of at least one of the first peak, the second peak, the third peak, and the fourth peak is 2.0 or less.
[0459] In the following table, in the "Elemental Analysis" column, the composition of the solid electrolyte (I) obtained in each reference example and the lithium-containing oxide in each comparative reference example is expressed as a relative value with the B content being set to "4.00" and expressed in terms of the molar amount of each element.
[0460] In the following table, "half width ratio (%)", "coefficient of determination" and "mass reduction rate (%)" are the same as those described in the above description of Reference Example 1.
[0461] In the following table, the “area intensity ratio” is the ratio of the above solid state 7 In the Li-NMR measurement, the ratio of the area intensity of the second peak to the area intensity of the first peak was measured, and the evaluation results were described based on the following criteria.
[0462] <Standards for the ratio of area strength>
[0463] A: When the area strength ratio is 15% or more
[0464] B: When the ratio of area strength is 0.5% or more and less than 15%
[0465] C: When the ratio of area intensity is less than 0.5%
[0466] In the following table, the "Maximum Absorption Intensity Ratio" column indicates whether the above infrared absorption spectrum characteristics are met. -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 When the maximum absorption intensity in the wave number region is greater than 0.20, it is represented as "A", and when it is less than 0.20, it is represented as "B".
[0467] In the following table, "-" means that the measured value is not shown.
[0468] [Table 3]
[0469]
[0470] [Table 4]
[0471]
[0472] As shown in the above table, it can be seen that the solid electrolytes (I)-5, (I)-6, (I)-7, (I)-8, (I)-9 and (I)-10 of Reference Examples 5 to 10 have excellent ion conductivity. In addition, according to the results of elemental analysis, it is confirmed that the content of Li in the solid electrolyte in Reference Examples 7 to 10 is higher. In Reference Examples 7 to 10, an aqueous dispersion containing a lithium oxide treated by mechanical grinding and an aqueous solution containing a lithium salt (method 3 in the above-mentioned step 2B) are mixed, and more lithium salt can be mixed. As a result, it is speculated that the amount of Li entering the solid electrolyte has increased. In addition, it can be seen that in Reference Examples 7, 8 and 9 using LiFSI as a lithium salt, the ion conductivity is further improved. It is speculated that this is because the increased Li contains Li with high mobility.
[0473] <Effect of water in solid electrolyte>
[0474] The solid electrolyte (I)-7 obtained in Reference Example 7 was vacuum dried under a constraint of 60 MPa and at 27°C, and the pressure change and ion conductivity with respect to the vacuum drying time were investigated. In addition, the method for preparing the powder body and the evaluation of ion conductivity were the same as described above, except that the In electrode was changed to a Ti electrode. The results are shown in Table 5.
[0475] [Table 5]
[0476]
[0477] The solid electrolyte (I)-7 of Reference Example 7 has a wavelength of 3000-3500 cm in the infrared absorption spectrum. -1 The OH stretching peak of the particles increases, so it is believed that a large amount of OH groups or water exists. In addition, regarding water, it is inferred that free water and bound water exist. In the above, the particles are first dried under conditions that are believed to volatilize from free water by vacuum drying, and then the particles are dried under strict drying conditions, so that the ion conductivity of each stage is evaluated.
[0478] As shown in the above table, the drying time was 5 minutes and the pressure was 200 Pa. It is considered that the free water was in a state of evaporation, but the ion conductivity showed 3.8×10 -3 S / cm, and the ionic conductivity showed 5.7×10 -4 S / cm. This result indicates that bound water in addition to free water exists and this contributes to ion conductivity.
[0479] [Reference Example 11]
[0480] In the same manner as in the preparation of the dispersion 1 in the above-mentioned Reference Example 7, a dispersion 9 having a concentration of 42% by mass of fine substances containing lithium oxide was obtained.
[0481] Next, 7.12 g of LiTFSI (chemical formula: Li(F 3 CSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 10 .
[0482] The obtained dispersion 9 and solution 10 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-11. The obtained powder was allowed to stand for a certain period of time in the atmosphere, and various evaluations were performed in the same manner as in Reference Example 5 using the solid electrolyte (I)-11 in the atmosphere. The results are summarized in the following table.
[0483] [Reference Example 12]
[0484] Solid electrolyte (I)-12 was obtained in the same manner as Reference Example 11 except that the contents of water and LiTFSI in the obtained solid electrolyte (I) were changed to the amounts described in the following table, and various evaluations were performed under air in the same manner as Reference Example 5. The results are summarized in the following table.
[0485] [Reference Examples 13 to 17]
[0486] Except that LiTFSI was changed to LiFSI and the contents of water and LiFSI in the obtained solid electrolyte (I) were changed to the amounts described in the following table, solid electrolytes (I)-13 to (I)-17 were obtained in the same manner as in Reference Example 11, and various evaluations were performed in the same manner as in Reference Example 5 under the atmosphere. The results are summarized in the following table. However, in Reference Example 17, the powder obtained by vacuum drying was immediately evaluated under the atmosphere.
[0487] In the following table, the columns "fine matter containing lithium oxide", "lithium salt" and "water" indicate relative molar ratios. For example, in Reference Example 11, the molar ratio of lithium salt to fine matter containing lithium oxide is 1, and the molar ratio of water to fine matter containing lithium oxide is 11. The above molar ratios were calculated by the following method.
[0488] Regarding the analysis of each element, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). Regarding N, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the Li salt, and regarding O, the analytical masses of elements other than O were added and calculated as a difference from the total amount of the solid electrolyte. In addition, in Reference Examples 11 and 12, regarding the carbon content, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the lithium salt. The molar ratio of the fine matter containing lithium oxide in the solid electrolyte to the lithium salt was calculated based on the molar ratio of the element (e.g., B) present only in the fine matter containing lithium oxide to the element present only in the lithium salt. In addition, the molar ratio of the fine matter containing lithium oxide to water was calculated by subtracting the molar ratio of O contained in the fine matter containing lithium oxide and the lithium salt from the molar ratio of O in the solid electrolyte, and the molar amount of O derived from water was calculated using the obtained molar amount of O derived from water and the molar amount of the fine matter containing lithium oxide.
[0489] [Table 6]
[0490]
[0491] Then, the content (mass %) of each component in the solid electrolyte (I) was calculated based on the molar amount and molecular weight described in Table 6. The results are shown in the following table.
[0492] [Table 7]
[0493]
[0494] [Table 8]
[0495]
[0496] As shown in the above table, the solid electrolyte of each reference example has desired characteristics or properties and exhibits excellent ion conductivity.
[0497] [Test Example 1]
[0498] <Winding durability test>
[0499] (Preparation of fine material containing lithium oxide)
[0500] 45 g of powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.), 770 g of zirconium oxide beads and 3 mL of water were placed in a 500 mL zirconium oxide jar and sealed with a Teflon (registered trademark) ring and a zirconium oxide lid. The LBO powder was pulverized at 300 rpm for 45 hours using a star ball mill to obtain a fine material containing lithium oxide.
[0501] (Preparation of solid electrolyte slurry)
[0502] 10 g of the lithium oxide-containing fine material, 15 g of water, and 11 g of LiFSI were mixed in a beaker and subjected to ultrasonic treatment for 30 minutes using an ultrasonic cleaner to obtain a dispersion. The dispersion was further stirred for 30 minutes using a magnetic stirrer to obtain a solid electrolyte slurry 1.
[0503] The solid electrolyte slurry 1 was vacuum dried at 40°C and 20Pa for 15 hours to obtain a powder. The obtained powder was stored in a desiccator (5%) for several days and then analyzed in the atmosphere. As a result, it was confirmed that the powder had the above-mentioned X-ray diffraction characteristics and was in an amorphous state. In addition, the ion conductivity was measured by the above-mentioned method and the result was 4.5×10 -3S / cm. The molar ratio of the content of LiFSI to the content of the lithium-containing oxide is 1, and the molar ratio of the content of water to the content of the lithium-containing oxide is 9. The element composition (molar ratio) is approximately as follows: Li:B:O:F:S:N=3:4:20:2:2:1.
[0504] (Preparation of positive electrode slurry)
[0505] 5.0 g of positive electrode active material LiCoO2 and 4.8 g of a 6 mass % aqueous dispersion of carbon nanotubes (CNT) (manufactured by KJ Specialty Paper Co., LTD.) as a conductive aid were added to 5.2 g of the above solid electrolyte slurry 1, and stirred for 30 minutes with a magnetic stirrer to obtain positive electrode slurry 1.
[0506] (Preparation of negative electrode slurry)
[0507] To 7.6 g of the above solid electrolyte slurry 1 were added 5.0 g of negative electrode active material TiNb2O7 and 9.8 g of a 6% aqueous dispersion of CNT (manufactured by KJ Specialty Paper Co., LTD.) as a conductive aid, and stirred for 30 minutes with a magnetic stirrer to obtain negative electrode slurry 1.
[0508] (Preparation of positive electrode side laminate [solid electrolyte layer / positive electrode active material layer / Al current collector])
[0509] Using a desktop coater, the above-mentioned positive electrode slurry 1 is coated on an A4-sized Al foil of 50 μm thick with a coating gap of 100 μm and a coating speed of 30 mm / s. After standing at room temperature for 1 hour, the above-mentioned solid electrolyte slurry 1 is multi-layered and coated on the positive electrode slurry coating film using a desktop coater with a coating gap of 200 μm and a coating speed of 90 mm / s. The multi-layer coating film is stored in a dryer with a relative humidity of less than 5% for 12 hours to dry, thereby obtaining a positive electrode side laminate (solid electrolyte layer / positive electrode active material layer / Al collector). In addition, the thickness of the solid electrolyte layer is about 60 μm.
[0510] (Preparation of negative electrode side laminate [solid electrolyte layer / negative electrode active material layer / Al current collector])
[0511] The negative electrode slurry 1 was coated on an A4-sized Al foil of 50 μm thick using a bench-top coater with a coating gap of 200 μm and a coating speed of 30 mm / s. After standing at room temperature for 1 hour, the solid electrolyte slurry 1 was coated on the negative electrode slurry coating film using a bench-top coater with a coating gap of 300 μm and a coating speed of 90 mm / s. The multilayer coating film was stored in a dryer with a relative humidity of less than 5% for 12 hours to dry, thereby obtaining a negative electrode side laminate (solid electrolyte layer / negative electrode active material layer / Al collector). In addition, the thickness of the solid electrolyte layer was about 60 μm.
[0512] (Winding durability test)
[0513] The positive electrode side laminate and the negative electrode side laminate are bonded together to form a battery element.
[0514] As a separator layer, a film made of Teflon (registered trademark) with a thickness of 50 μm was laminated and pressed to obtain a battery element laminate.
[0515] The battery element laminate was spirally wound four times around a core material having a diameter of 3 mm, with the separator layer side facing the inner side, so that the battery element had four layers.
[0516] Next, the wound body was unrolled and stretched, and visually observed, and as a result, no cracks were generated in the solid electrolyte layer.
[0517] Then, the battery element stack is wound around a core material to produce a Figure 2 As a result, it was confirmed that the wound secondary battery shown was chargeable and dischargeable and could function as a secondary battery.
[0518] Thus, the secondary battery of the present invention has been shown to have excellent bonding between particles, is less likely to crack even when wound on a chip, and does not generate harmful substances, thus having excellent safety, although using an oxide-based solid electrolyte.
[0519] The present invention has been described together with its embodiments, but unless otherwise specified, it is understood that the present invention should not be limited to any details in the description and should be broadly interpreted within the scope of the spirit of the invention shown in the attached technical solutions.
[0520] This application claims priority based on Japanese Patent Application No. 2022-089963 filed in Japan on June 1, 2022, the contents of which are incorporated herein by reference as a part of what is described in this specification.
[0521] Explanation of symbols
[0522] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state lithium-ion secondary battery, 21-stack, 21a-diaphragm layer, 21b-negative electrode collector, 21c-negative electrode active material layer, 21d-solid electrolyte layer, 21e-positive electrode active material layer, 21f-positive electrode collector, 23-battery outer casing, 25-positive electrode sheet, 26-battery positive electrode, 27-negative electrode sheet, 28-battery negative electrode, 30-wound all-solid-state lithium-ion secondary battery.
Claims
1. A wound all-solid-state lithium-ion secondary battery, which is formed by winding a laminated body in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are sequentially arranged on a core material, wherein: The solid electrolyte layer includes a solid electrolyte in an amorphous state, wherein the solid electrolyte in an amorphous state includes a lithium-containing oxide including Li, B and O and a lithium salt, In the amorphous solid electrolyte, the content of the lithium salt relative to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio.
2. The wound all-solid-state lithium-ion secondary battery according to claim 1, wherein: In the amorphous solid electrolyte, a ratio of the content of water to the content of the lithium-containing oxide is 12 or less in terms of molar ratio.
3. The wound all-solid-state lithium-ion secondary battery according to claim 2, wherein: In the amorphous solid electrolyte, the content of water relative to the content of the lithium-containing oxide is 1 to 12 in terms of molar ratio.
4. The wound all-solid-state lithium-ion secondary battery according to any one of claims 1 to 3, wherein The lithium-containing oxide comprises Li 2+x B 4+y O 7+z , Among them, -0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.
3.
5. The wound all-solid lithium ion secondary battery according to any one of claims 1 to 4, wherein The lithium salt is represented by the following formula (1): Formula (1) LiN(R f1 SO2)(R f2 SO2) In the formula, R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.
6. The wound all-solid lithium ion secondary battery according to any one of claims 1 to 5, wherein In the amorphous solid electrolyte, when the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49, the molar amount of O is 6.23 to 25.00, and the molar amounts of elements other than B, Li, and O are 0.001 to 10.00, respectively.
7. The wound all-solid lithium ion secondary battery according to any one of claims 1 to 6, wherein The lithium-containing oxide is an oxide that has been subjected to mechanical grinding.
8. A wound all-solid-state lithium-ion secondary battery, which is formed by winding a laminated body in which a positive electrode layer, a solid electrolyte layer and a negative electrode layer are sequentially arranged on a core material, wherein: The solid electrolyte layer contains an amorphous solid electrolyte including Li, B and O. When the molar amount of B in the amorphous solid electrolyte is set to 4.00, the molar amount of Li is 1.58 to 3.49, the molar amount of O is 6.23 to 25.00, and the molar amounts of elements other than Li, B and O are 0.001 to 10.00, respectively.
9. A method for manufacturing a wound-type all-solid-state lithium-ion secondary battery according to any one of claims 1 to 8, comprising the following steps: The stacked body is formed under the condition that the solid electrolyte layer is in contact with moisture.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A
